Essential oils for grain protection and behavioral responses of Zabrotes subfasciatus - Rodrigo Donizeti Faria; Edson Luiz Lopes Baldin; Leandro do Prado Ribeiro; Thiago Luis Martins Fanela; Isabella Rubio Cabral; Vinicius Fernandes Canassa; Antônio Eduardo Miller Crotti; Thaís Aparecida dos Santos Oliveira; Renata Takeara; Wagner Antonio Bernardes; Carlos Gilberto Raetano (Crop Protection, 2026)

Genomic analysis of Escherichia coli, Enterobacter hormaechei, and Cupriavidus gilardii isolated from Cacatua alba - Julia Penna de Andrade; Henrique da Silva Vieira; Camilla Faria Soares; Marcela Laryssa Oliveira Duarte; André Almeida Fernandes; Hannah Luiza Gonsalves Coelho; Victória Veiga Alves; Bertram Brenig; Vasco Ariston de Carvalho Azevedo; Flávia Figueira Aburjaile; Nelson Rodrigo da Silva Martins (Veterinary Research Communications, 2026)
The objective of this study was to perform genomic, phylogenomic, and phenotypic characterization of bacterial isolates from a captive Cacatua alba to investigate their antimicrobial resistance profiles, virulence-associated genes, and genomic relationships with publicly available strains. Bacterial isolates obtained from the lungs and encephalon were identified as Escherichia coli (AV037), Enterobacter hormaechei (AV038), and Cupriavidus gilardii (AV039). Comparative genomic analyses, phylogenomic reconstruction, and antimicrobial susceptibility testing (AST) were performed. Genomic analysis identified multiple antimicrobial resistance-associated genes in AV037, AV038, and AV039, with genes associated with efflux pumps, particularly those in the resistance-nodulation-cell division (RND) family, as the predominant resistance-associated mechanism identified. Most identified genes are intrinsic to the respective bacterial species and do not necessarily confer phenotypic antimicrobial resistance when present alone. Phenotypic testing confirmed multidrug-resistant (MDR) profiles, with resistance to β-lactams and aminoglycosides. Susceptibility to carbapenems was preserved in AV037 and AV038, whereas AV039 exhibited resistance to meropenem. Phylogenomic analysis demonstrated that AV037 and AV038 clustered with strains recovered from diverse hosts and geographic regions. In contrast, AV039 clustered predominantly with environmental and human-associated isolates, including strains harboring the mcr-5 gene. These findings are consistent with previous reports describing the recovery of C. gilardii from both environmental and clinical sources. Overall, this study documents the occurrence of MDR bacteria carrying resistance and virulence-associated determinants in a captive C. alba , highlighting the value of genomic surveillance to improve our understanding of the distribution of clinically relevant bacterial isolates across different ecological settings.

Molecular characterization of extended-spectrum β-lactamases-producing Escherichia coli isolated from patients with bacteremia - Beatrice D. V. L. Souza; Guilherme Solveira; Guilherme F. R. de Souza; Henrique Orsi; Daiany R. P. De Lira; Iranildo do A. Fernandes; Adriano M. Ferreira; Alessandro L. Mondelli; Claudio T. Sacchi; Karoline R. Campos; Marlon B. N. Santos; Carlos H. Camargo; et al. (Brazilian Journal of Microbiology, 2026)
Bacteremia is a major health problem that affects millions of people worldwide. E. coli is one of the main pathogens associated with bacteremia and its resistance to the antimicrobial drugs, including β-lactams, has significantly increased in recent years. In view of the above, our objective was to determine the antimicrobial resistance profile of 60 E. coli isolates obtained from patients with bacteremia, as well as to characterize extended-spectrum β-lactamases (ESBL) -producing isolates. The highest resistance rates were observed for ciprofloxacin (33.3%), levofloxacin (31.7%), cefuroxime (20%) and cefotaxime (20%). Furthermore, 12 isolates (20%) were ESBL producers. Genomic analysis showed that 58.3% of these ESBL-producing isolates belonged to the phylogroup B2, ST131, serotype O25:H4 and carried the following ESBL-encoding genes: bla CTX−M−15 (66.7%), bla CTX−M−8 (16.7%), bla CTX−M−2 (8.7%) or bla CTX−M−27 (8.7%). Our data highlight the high frequency of E. coli ST131 among the ESBL-producing isolates obtained from patients with bacteremia in Botucatu, Brazil.

Correction: Caracterização taxonômica integrativa de comunidades bacterianas e fúngicas de tripas de cupins e areia de folhas - Suzan Prado Fernandes Bernal; Célia Soares; Júlia Ronzella Ottoni; Caroline da Costa Silva Gonçalves; Nelson Lima; Michel Rodrigo Zambrano Passarini (Brazilian Journal of Microbiology, 2026)

Integrative taxonomic characterization of bacterial and fungal communities from termite guts and leaf litter - Suzan Prado Fernandes Bernal; Célia Soares; Júlia Ronzella Ottoni; Caroline da Costa Silva Gonçalves; Nelson Lima; Michel Rodrigo Zambrano Passarini (Brazilian Journal of Microbiology, 2026)

Methylation analysis of LINE-1 elements in canine cutaneous mast cell tumors - Guilherme Bogdanov Giorgini; José Guilherme Xavier; Rodrigo Augusto Foganholi da Silva; Eduardo Fernandes Bondan (Topics in Companion Animal Medicine, 2026)

Developmental effects of intrauterine and lactational exposure to nanoplastics and phthalates on rat testis - Mirella Franco Moreira; Natália Magosso; Patrick Vieira de Souza; Matheus Naia Fioretto; Isabela Silva Ferreira; Vanessa Aguiar Rocha; Victória Cristina Pinha; Débora Hipólito Quadreli; Glaura Scantamburlo Alves Fernandes; Luis Antonio Justulin; Jodi Anne Flaws; Wellerson Rodrigo Scarano (Environmental Pollution, 2026)

Anatomopathological aspects of osteoarticular lesions associated with Rhodococcus equi infection in two foals - Felipe Martins Pastor; Suzyane Oliveira Barros; Letícia Fernandes Campos; Acácia Eduarda de Jesus Nascimento; Gabriel Henrique Guimarães; Carlos Renato de Souza Guimarães Filho; Luis Ernesto Campos Torres; Pâmela Aparecida de Lima; Andressa Batista da Silveira Xavier; Rodrigo Otávio Silveira Silva; Roberto Maurício Carvalho Guedes; Rogéria Serakides; et al. (Veterinary Research Communications, 2026)
Rhodococcus equi is an important bacterium that affects foals up to six months of age, especially those that are immunocompromised. The main manifestation is pyogranulomatous pneumonia; nevertheless, extrapulmonary lesions have not only been reported, but are not uncommon, including arthritis and osteomyelitis. Despite the widespread occurrence of rhodococcosis, the macro- and microscopic lesions in the musculoskeletal system are still poorly understood, and a detailed study is needed to better understand the pathogenic potential of the organism. The aim of this report is to present the anatomopathological aspects of bone and joint lesions associated with Rhodococcus equi in two foals. The first case was a two-month-old male Quarter Horse foal with suspected cervical trauma. This horse was admitted in lateral recumbency, semi-comatose, and with atlantoaxial region enlarged. Necropsy revealed atlantooccipital arthritis with pyogranulomatous osteomyelitis, resulting in pathologic fractures of the atlas. There was also pyogranulomatous pachymeningitis leading to compressive myelopathy. In the second case, a two-month-old Brazilian Sport Horse foal presented with lameness of the left pelvic limb and enlargement of the left femorotibial and femoropatellar and right scapulohumeral joints. Necropsy revealed femorotibial and femoropatellar arthritis and purulent osteomyelitis in the femur, as well as extensive necrosis and bone rarefaction with focal detachment of the epiphyseal plate. Both animals had pyogranulomatous pneumonia and lymphadenitis with extracellular and intracytoplasmic gram-positive coccobacilli in neutrophils and macrophages. In the first case, R. equi was isolated and confirmed by MALDI-TOF. R. equi infection should be considered in the differential diagnosis of osteoarticular lesions in foals.

Association of the endosomal TLR4 pathway with dorsolateral prostatic remodeling induced by perinatal phthalate mixture exposure in rats - Vinícius Luís Rocha da Silva Maria; Ana Clara Pacheco de Santana; Patrick Vieira Souza; Vanessa Aguiar Rocha; Matheus Naia Fioretto; Natália Magosso; Mirella Franco Moreira; Maria Clara Betete Da Silva Fonseca; André Mascarenhas Guariento; Sergio Pereira; Ariana Musa Aquino; Letícia P. Bomfim; et al. (Reproductive Toxicology, 2026)

Large-scale toxic bloom of Dinophysis acuminata complex following a major flood disaster in southern Brazil - Luiz L. Mafra; Bruna Fernanda Sobrinho; Ana Martínez; Karoline Magalhães F. Lubiana; Regiane Valejo Maciel; José Guilherme F. Bersano; Luciano F. Fernandes; Fabiola Kaviatkovski; Pedro Almeida Rodrigo; Rafaela Cristine Zem; Carlos E.J.de Azevedo Tibiriçá; Mathias Alberto Schramm; et al. (Harmful Algae, 2026)

Comparative effects of Vitex agnus-castus and estradiol on bone tissue and osteoblasts under estrogen-deficient and oxidative stress conditions. - Maria Carolina Coelho; Luiz Gabriel Plasier Guedes de Mello; Yasmin Tavares Camargo; Roger Rodrigo Fernandes; Sayuri Poli Suguimoto; Roberta Okamoto; Selma Siessere; Karina Fittipaldi Bombonato-Prado (Tissue and Cell, 2026)

Cork barriers combined with surfactant-assisted electrokinetics for remediation of diesel-contaminated soils - Paula V. Remor; Sónia A. Figueiredo; Virgínia Cruz Fernandes; Manuel A.R. Rodrigo; Vítor J.P. Vilar (Journal of Environmental Management, 2026)

Meta-analysis of woody plant diversity and aboveground biomass stock co-benefits across Amazon agroforestry systems - Thamires Campos de Almeida; Silvio Nolasco de Oliveira Neto; Arthur da Cruz Silva; Rodrigo Gomes Gorsani; Lorena Evangelista Fernandes; Sebastião Venâncio Martins; Mehdi Heydari; Andrés Iván Prato; Lisandra Mendes Louzada-Camilo; Ana Luiza Rangel; Jamerson Souza da Costa; Alisson Lopes Rodrigues; et al. (Agroforestry Systems, 2026)

Resistance Mechanisms in Cucumis melo (L.) Genotypes to Bemisia tabaci MED (Hemiptera: Aleyrodidae) - Vinicius Fernandes Canassa; Felipe Savieto Furquim de Souza; Roberta Wagner de Oliveira; Aline Marques Pinheiro; Rodrigo Donizeti Faria; Isabella Rubio Cabral; Cristiano Soleo Funari; Martin Kássio Leme da Silva; Valter Rodrigues Oliveira; André Luiz Lourenção; Carlos Gilberto Raetano (Journal of Crop Health, 2026)

Using La2O3/Printex carbon cathode for simultaneous H2O2 generation and synergistic amitriptyline degradation in aqueous matrices - F. Escalona-Durán; C.H.M. Fernandes; G.O.S. Santos; R.J.A. Felisardo; W.R.P. Barros; R. Colombo; M.A. R. Rodrigo; M.R.V. Lanza (Process Safety and Environmental Protection, 2026)

Enhancing coffee plant growth using Aspergillus niger in phosphorus-fixing soil: insights from biometric and remote sensing analysis - Ana Laura Campos AIRÃO; Gustavo de Souza Marques MUNDIM; Gleice Aparecida de ASSIS; Rodrigo Bezerra de Araújo GALLIS; Izaura Martins FERNANDES; Renan ZAMPIROLI; Gilberto de Oliveira MENDES (Pedosphere, 2026)

Paternal exposure to low-dose N-nitrosodimethylamine (NDMA) induces intergenerational alterations in the prostatic microenvironment of rats - Karen Gabriela Favaro de Souza; Gabrielle Chalupa Faria; Débora Hipólito Quadreli; Ivana Regina da Costa; Bárbara Campos Jorge; Lívia Trippe Nagaoka; Julia Stein; Vanessa Aguiar Rocha; Arielle Cristina Arena; Wellerson Rodrigo Scarano; Glaura Scantamburlo Alves Fernandes (Food and Chemical Toxicology, 2026)

Reassessing and Updating Regulatory Standards on the Declaration of Storage Conditions in the Product Information of Medicinal Products: An Evidence-Based Proposal under EMA Guidance - Helena Pericão; Henrique Cavaco; Miguel Dias; Luís Sarmento; Mário Magalhães; Bernardo Filipe; Herivelto Vieira; João Rita; Pedro Gonçalves; Matilde Vaz; Beatriz Coimbra; Beatriz Monteiro; et al. (Pharmaceutical Research, 2026)
Purpose The European Medicines Agency (EMA) guideline Declaration of Storage Conditions in the Product Information of Medicinal Products (CPMP/QWP/609/96/Rev.2) was last revised in 2007. Since then, advances in stability science, increased climatic variability, and evolving regulatory expectations have highlighted limitations in the framework, particularly the use of vague descriptors such as “room temperature” or “no special storage conditions.” This work reassesses the scientific and regulatory basis for storage statements, integrating current understanding of mean kinetic temperature (MKT), climate-related risks, and developments in ICH and WHO guidance, and proposes a harmonized revision (Rev.3). Methods A structured analysis of regulatory and scientific principles was conducted, incorporating MKT, climate-related risks, and developments in ICH and WHO guidance. These elements informed a revised framework and model storage statements, including a decision table linking stability outcomes to label statements. Results The proposed update introduces explicit temperature-based statements, strengthens the linkage between stability data and label wording, clarifies requirements for moisture- and light-sensitive products, expands guidance for sterile and reconstituted preparations, and provides contingency instructions for temperature excursions. A decision table mapping stability outcomes to label statements is included to support regulatory implementation. Conclusion This revision provides an updated synthesis of EMA, ICH, and WHO requirements, translating regulatory principles into clear storage statements and contingency guidance. It offers a more precise framework reducing ambiguity, supports justification of storage conditions through stability data and MKT-informed risk assessment, aiming to improve understanding among patients and healthcare professionals, strengthening real-world product quality and contributing to future EMA guideline development. Highlights Identifies scientific and regulatory limitations in current “no special storage conditions” terminology; Links ICH stability guidelines and climatic variability to precise storage statements; Proposes harmonised core label phrases for room temperature, fridge, and freezer; Introduces contingency labelling for climate-related and cold-chain excursions.

Correction: Pretreatment of lignocellulosic biomass and biogas production from a microbial consortium recovered from soil litter and termite gut - Suzan Prado Fernandes Bernal; Leiber Julio Granada Galvis; Júlia Ronzella Ottoni; Nelson Lima; Márcia Regina Becker; Caroline da Costa Silva Gonçalves; Michel Rodrigo Zambrano Passarini (World Journal of Microbiology and Biotechnology, 2026)

Microplastic ingestion in demersal and benthic species from the Portuguese coast: Scyliorhinus canicula, Trisopterus luscus, Polybius henslowii - Rodrigo Pica; João Fernandes; Sónia Seixas; Marta Martins (Marine Environmental Research, 2026)

Innovative microparticle strategies: harnessing essential oil-loaded lecithin/chitosan systems against Burkholderia pseudomallei - Anderson da Cunha Costa; Dayana Pinto de Meneses; Maria Rosiene Antunes Arcanjo; Mirele Rodrigues Fernandes; Augusto Feynman Dias Nobre; Alanna Mayara Soares de Sousa; Rosemayre Souza Freire; João Victor Serra Nunes; Thomas Crouzier; Ulrike Schimpf; Rodrigo Silveira Vieira; Raimunda Sâmia Nogueira Brilhante (Biofouling, 2026)

Alternative strategic control of Rhipicephalus microplus in the Cerrado of Minas Gerais, Brazil, by exploiting abiotic conditions - Vinicius da Silva Rodrigues; Maria Clara Oliveira Sousa; Rodrigo da Costa Maia; Giovanna Cirqueira Ribeiro Borges; Amanda Ferreira Rezende; Ana Carolina Sousa; Gustavo Martins Felix Silva; Adriane Suzin; Matheus Augusto Ferreira Fernandes; Matias Pablo Juan Szabó (Veterinary Parasitology, 2026)

On the importance of soil texture for predicting future global soil respiration - Lucas Carvalho Gomes; Cássio Marques Moquedace; Ivan F. Souza; Ben Bond-Lamberty; Rodrigo Vargas; Lars Vesterdal; Gustavo V. Veloso; Marcio Rocha Francelino; Carlos E.G.R. Schaefer; Kendalynn A. Morris; Elpídio I. Fernandes-Filho (Science of The Total Environment, 2026)

Sustainable oxygen-functionalized graphitic carbons from agro-waste: Influence of biomass source on atenolol removal - Nathália Magno Galdino; Mayara Bitencourt Leão; Rodrigo Morawski; Alexandre G. Brolo; Andreia Neves Fernandes; Jacqueline Ferreira Leite Santos (Journal of Environmental Chemical Engineering, 2026)

What are the toxicological effects of mixing nanoplastics with a nanopesticide on Daphnia magna and Aliivibrio fischeri? - Thuanne Braúlio Hennig; Felipe Ogliari Bandeira; Heloísa Gabe; Rodrigo Costa Puerari; Denice Schulz Vicentini; Alcir Luiz Dafré; Leonardo Fernandes Fraceto; William Gerson Matias (Aquatic Toxicology, 2026)

Invasive Fishes Interact With Temperature to Reshape Community Size Structure Across Climatic Zones - Barbbara Silva Rocha; Ignasi Arranz; Henrique C. Giacomini; Daniel M. Perkins; Gilberto Nepomuceno Salvador; José Luís Costa Novaes; Jorge Iván Sánchez‐Botero; Angelo Antonio Agostinho; Paulo Santos Pompeu; Rosemberg Fernandes Menezes; Silvia Yasmin Lustosa‐Costa; Telton Pedro A. Ramos; et al. (Global Change Biology, 2026)
The body size spectrum (or individual size distribution) is a simple yet widely recognized approach that links individual and population traits to community structure and ecosystem functions, making it a valuable indicator of anthropogenic effects. However, the assessment of size spectra in the context of biological invasions remains poorly explored. We investigated the impacts of non‐native (NN) fish invasions on the size structure of 667 lacustrine fish communities across climatic regions (temperate, tropical, and subtropical systems) and the roles of trophic position and temperature in modulating these effects. We found that fish communities under higher invasion pressure exhibit flatter, or less negative, size spectrum exponents. Also, NN species from lower trophic levels can have greater impacts than piscivorous NNs by reshaping size spectra and reducing the overall biomass of native communities. We also observed that piscivore NNs and NNs from lower trophic levels interacted positively with temperature to drive the size spectrum exponent and total biomass of the native communities, respectively. These results can be explained by two main mechanisms: (i) NN piscivores primarily act through size‐selective predation (top–down control), which may be intensified particularly on small prey in warmer lakes, and (ii) NN fish from lower trophic levels primarily act through competition, hence reducing the numerical abundance of small‐sized native fish, which may be more vulnerable in colder and less productive lakes. These mechanisms are leading to flatter size spectrum exponents mainly at higher temperatures and to a decline in the total biomass of the native community, mainly at lower temperatures, effectively reversing the expected temperature–size rule pattern. By disentangling the trophic and temperature‐dependent mechanisms through which NN fishes affect size structure, this study strengthens our ability to anticipate the impact of biological invasions on freshwater communities and their ecosystem functions and services under global change.

Impact of PM2.5 on cardiorespiratory mortality: A study in the capitals of Brazilian amazon rainforest - Gustavo de Oliveira Silveira; Rodrigo de Lima Brum; Ronan Adler Tavella; Alicia da Silva Bonifácio; Ronabson Cardoso Fernandes; Flavio Manoel Rodrigues da Silva Júnior (Toxicology, 2026)

Soil quality and soybean yield responses to occasional subsoiling and crop system diversification in a consolidated no-tillage system - Cristiano Alves da Silva; Rodrigo Arroyo Garcia; Michely Tomazi; Elaine Reis Pinheiro Lourente; Sérgio Augusto Rodrigues; Dirceu Maximino Fernandes (Soil and Tillage Research, 2026)

Agricultural use of water and nutrients from the saline industry effluent in the semi-arid region of potiguar: interrelationships of soil attributes and physiological indices of forage sorghum - Diego José da Costa Bandeira; Jeane Cruz Portela; Rafael Oliveira Batista; Blake Charles Diniz Marques; Joaquim Emanuel Fernandes Gondim; Jussiara Sonally Jácome Cavalcante; Maria Clara Correia Dias; Antônio Gustavo de Luna Souto; José Francismar de Medeiros; Rodrigo Rafael da Silva; Paulo Jardel Mota; Geisiane Xavier de Matos; et al. (Water, Air, & Soil Pollution, 2026)

Enhanced H2O2 electrogeneration for simultaneous degradation of multiple pharmaceuticals and validation in real water using UVC-assisted processes - Raul José Alves Felisardo; Florymar Escalona Durán; Carlos Henrique Magalhães Fernandes; Géssica de Oliveira Santiago Santos; Renata Colombo; Manuel Andrés Rodrigo Rodrigo; Marcos Roberto de Vasconcelos Lanza (Chemical Engineering Journal, 2026)

Longitudinal study of frequency of diarrhea and rotavirus species A in suckling calves from a small-scale family dairy farm in Brazil - Geovana Depieri Yoshitani; André de Sá Ribeiro; Elisabete Takiuchi; Rodrigo Alejandro Arellano Otonel; Juliana Torres Tomazi Fritzen; Alice Fernandes Alfieri; Amauri Alcindo Alfieri (Veterinary Research Communications, 2026)

First cerrado record of Charletonia rocciai (Trombidiformes: Erythraeidae) on a flea beetle (Coleoptera: Chrysomelidae), with notes on its distribution - Bruno Piotrovski Begha; Tiago Tosta Fernandes Pereira; Beatriz Lira-Pereira; Vanessa Leonel Falchi; Rodrigo Damasco Daud; Sarah Siqueira Oliveira; Ricardo Bassini-Silva; Fernando de Castro Jacinavicius (Biologia, 2026)

Chemical characterisation, thermal analysis, and antibacterial activity of honeys from Caatinga stingless bees of Melipona spp. - Niedja Eloi de Sousa Guimarães; Myllena Larissa Salles Oliveira; Davi Nathan Fernandes dos Santos; Rodrigo Gonçalves de Araújo; Ana Clara Vieira da Cunha; Jessé de Oliveira da Silva; Felipe Hugo Alencar Fernandes (Natural Product Research, 2026)

Larvicidal efficacy of Varronia curassavica leaf phytochemicals against Aedes aegypti: anatomical, histological and cytotoxic analyses - Marcela Rezende Cordeiro; Saulo Pireda; Maria Aparecida Aride Bertonceli; Thalya Soares Ribeiro Nogueira; Nicolly Lopes Bautz; Rodrigo Barbosa Braga Feitoza; Felipe Figueirôa Moreira; Ivo José Curcino Vieira; Carlos Roberto Ribeiro Matos; Raimundo Braz-Filho; Sergio Henrique Seabra; Francisco José Alves Lemos; et al. (Pesticide Biochemistry and Physiology, 2026)

Pretreatment of lignocellulosic biomass and biogas production from a microbial consortium recovered from soil litter and termite gut - Suzan Prado Fernandes Bernal; Leiber Julio Granada Galvis; Júlia Ronzella Ottoni; Nelson Lima; Márcia Regina Becker; Caroline da Costa Silva Gonçalves; Michel Rodrigo Zambrano Passarini (World Journal of Microbiology and Biotechnology, 2026)

A Low-Cost, Open-Source, Multi-Purpose Autonomous Surface Vehicle - Thomaz Augusto Kras Benatti; Emerson Martins de Andrade; Maicon Rodrigo Correa; Felipe da Silva Lopes; João Paulo Machado dos Santos Bernardino; Joel Sena Sales; Antonio Carlos Fernandes (Journal of Marine Science and Engineering, 2025)
Autonomous surface vehicles (ASVs) have played a crucial role in various areas, including oceanographic research, environmental monitoring, and asset inspection. However, the high cost and proprietary nature of many platforms limit accessibility. Thus, this work introduces a low-cost, fully open-source ASV platform designed to support a wide range of applications, from academic research to community-driven monitoring projects, bridging the existing gap between low-cost prototyping and naval architecture-based ASV development. Featuring a modular 2 m hull design, the vehicle integrates off-the-shelf components and open-source software to ensure affordability, flexibility, and ease of replication. Field tests were conducted on Ilha do Fundão (Fundão Island), located within the campus of the Federal University of Rio de Janeiro (UFRJ), Brazil. All design files and code are released on GitHub (version 1.0.0) to encourage adoption and collaborative improvement.

Synthesis and characterization of a clay-coal waste-based adsorbent for contaminant removal from acid mine drainage - Laura Alessandra Prado Milani; Lívia Fernandes; Eduardo Alberton Ribeiro; Rodrigo Battisti; Vilmar Menegon Bristot; Agenor De Noni Jr; Dachamir Hotza; Marcelo Dal Bó (Minerals Engineering, 2025)

Petrogenesis and emplacement of the Paleoproterozoic A-type Marajoara granite in the Carajás province, southeastern Amazonian craton: Constraints from geochemistry, zircon geochronology, Nd Hf isotopes, coexistence of reduced and oxidized magmas and new insights from a composite dike - Rodrigo Fabiano Silva Santos; Davis Carvalho de Oliveira; José de Arimatéia Costa de Almeida; Roberto Dall'Agnol; Bhrenno Marangoanha; Marco Antonio Galarza; Cláudio Nery Lamarão; Fernando Fernandes da Silva (Lithos, 2025)

The Pilates Method reduces blood pressure and increases respiratory strength and cardiorespiratory capacity in medicated hypertensive women - Rodrigo Fernandes Barbosa; Moisés Felipe Pereira Gomes; Daniele Tavares Ruider; Bruno Rodrigues; Alan Carlos Brisola Barbosa; Victor Zuniga Dourado; Alessandra Medeiros (European Journal of Applied Physiology, 2025)

Antimicrobial resistance and biofilm production by Staphylococcus spp. and Mammaliicoccus sciuri in Inia araguaiaensis: surveillance under a one health perspective in the Amazon - Denny Parente de Sá Barreto Maia Leite; Pollyanne Raysa Fernandes de Oliveira; Flavia Cristina Matos Oliveira; Gabriel Melo-Santos; Guilherme Maricato; Karolina Rosa Fernandes Beraldo; Angélica Lúcia Figueiredo Rodrigues; Alexsandro Antonio Portilho Damasceno; Rodrigo Hipólito Tardin Oliveira; Thais Fernanda Campos Fraga-Silva; Maria Aparecida Juliano; Frederico Ozanan Barros Monteiro; et al. (Veterinary Research Communications, 2025)

The effect of turbidity on predator–prey interactions between invasive fish species - Rodrigo Fernandes; Fernando Mayer Pelicice; Eveline de Almeida Ferreira; Carlos Walker Fernandes Menezes; Victor Neudo Santos Tavares (Environmental Biology of Fishes, 2025)

Compensatory growth and physiological responses of matrinxã (Brycon amazonicus) under cyclic feed restriction - Márcia Simões dos Santos; Ariany Rabello da Silva Liebl; Ellan Rodrigo Monteiro Paes Fernandes; Christiane Patricia Feitosa de Oliveira; João Paulo Ferreira Rufino; Maria Fernanda Silva Gomes; Rayana Melo Paixão; Aline da Cunha Ferreira; Fernanda Victoria Nery Dias; Adriano Teixeira de Oliveira (Aquaculture International, 2025)

Cannabidiol potentiates phenobarbital-induced cell death in the developing brain - Rubia Aparecida Fernandes; João Vitor Melo Ribeiro; Rodrigo Espindula Torres; Giovanna Bruno Borges; Larissa Gabrielly Ribeiro de Freitas; Olagide Wagner de Castro; Marcio Flávio Dutra Moraes; Norberto Garcia-Cairasco; Fabrício A. Moreira; Victor Rodrigues Santos (NeuroToxicology, 2025)

210Pb chronology assessing the historical microplastics dynamics and aging effects in urban areas with separate sewer systems and multiple-use reservoir - Fabiano T. Conceição; Alexandre M. Fernandes; Sarah G. Lacerda; Rodrigo B. Moruzzi; Naiara O. Santos; Rosa Busquets; Luiza C. Campos (Journal of Hazardous Materials, 2025)

Biodiversity baseline assessment for offshore wind projects: Challenges to implement Ecosystem-Based management - Ivan Rodrigo Abrão Laurino; Luciana Yokoyama Xavier; Allan Yu Iwama; Monique Fogaça Fernandes; Lucas Bernardinelli de Souza; Marcia Regina Denadai; Luis Enrique Sánchez; Alexander Turra (Journal for Nature Conservation, 2025)

Simulating Carbon Mineralization at Pore Scale in Capillary Networks of Digital Rock - David A. Lazo Vasquez; Jaione Tirapu Azpiroz; Rodrigo Neumann Barros Ferreira; Ronaldo Giro; Manuela Fernandes Blanco Rodriguez; Matheus Esteves Ferreira; Mathias B. Steiner (Transport in Porous Media, 2025)
Predicting the geometrical evolution of the pore space in geological formations due to fluid–solid interactions has applications in reservoir engineering, oil recovery, and geological storage of carbon dioxide. However, modeling frameworks that combine fluid flow with physical and chemical processes at a rock’s pore scale are scarce. Here, we report a method for modeling a rock’s pore space as a network of connected capillaries and to simulate the capillary diameter modifications caused by reactive flow processes. Specifically, we model mineral erosion, deposition, dissolution, and precipitation processes by solving the transport equations iteratively, computing diameter changes within each capillary of the network simultaneously. Our automated modeling framework enables simulations with digital rock samples as large as (1.125 mm) $$^3$$ 3 having 125 $$×$$ × 10 $$^6$$ 6 voxels, within seconds of CPU time per iteration. As an application of the computational method, we have simulated brine injection and calcium carbonate precipitation in sandstone. For quantitatively comparing simulation results obtained with models predicting either a constant or a flow rate-dependent precipitation, we track the time-dependent capillary diameter distribution as well as the permeability of the connected pore space. For validation and reuse, we have made the automated simulation workflow, the reactive flow model library, and the digital rock samples available in public repositories.

The Impact of Biological Sex And High-Fat High-Fructose Diet on Brain Dysfunction in an Animal Model of Sepsis - Andriele Vieira; Mariane Abatti; Monique Michels; Amanda Goulart; Cristiano Julio Faller; Heloisa Borges; Filipe Fernandes; Diogo Dominguini; Luana Rocha; Emily Córneo; Rodrigo Dias; Felipe Dal-Pizzol (Molecular Neurobiology, 2025)

Paraprobiotics Mitigate Inflammation and Anxiety-Like Behavior in a Lipopolysaccharide-Induced Mouse Model - Monique Michels; Gabriel Fernandes Alves Jesus; Emily Córneo; Luana Bezerra Rocha; Rodrigo Dias; Ana Paula Lorenzen Voytena; Marina Piola Rossetto; Fernanda Ramlov; Felipe Dal-Pizzol; Ana Paula Pesarico (Current Microbiology, 2025)

Metabolic brain changes in post-acute COVID-19: systematic review and meta-analysis of [18F]-FDG-PET findings - Izabella Fernanda Bastos Siqueira; Lais Almeida Figueiredo; Camila Emanuele Moreira Fernandes; Leandro Pinheiro Cintra; Glauber Fernandes de Oliveira; Maria Angélica Rios; Ricardo Maciel; Rodrigo Ferretjans; Nathalia Sernizon Guimarães; Luiz Alexandre Viana Magno (Brain Structure and Function, 2025)

Maternal exposure to phthalates and nanoplastics, isolated or combined: Impacts on placental structure, development, and antioxidant defense as a trigger for maternal-fetal adversities - Natália Magosso; Patrick Vieira Souza; Mirella Franco Moreira; Vanessa Aguiar Rocha; Matheus Naia Fioretto; Victória Cristina Pinha; Gabriel Aquino Maia; Vinícius Luís Rocha S. Maria; Luisa Annibal Barata; Giovanna Fachetti Frigoli; Glaura Scantamburlo Alves Fernandes; Arielle Cristina Arena; et al. (Reproductive Toxicology, 2025)

Bioprecipitation of calcium carbonate by Antarctic endolithic bacteria: biotechnological applications - Susana Patricia Lotero Arcila; Gabriel Neumann Magalhães; Reinaldo Santos Shimabuku Junior; Edna Possan; Pablo Henrique Nunes; Alysson Wagner Fernandes Duarte; Luiz Henrique Rosa; Michel Rodrigo Zambrano Passarini (World Journal of Microbiology and Biotechnology, 2025)

Effects of zinc oxide and monoglyceride blend on intestinal immune, health and microbiota responses of weanling pigs - Ana Lígia Braga Mezzina; Erick Marlon Pereira; Cecília Archangelo Ferreira de Melo; Thallysson Taumaturgo Silva Souza; Matheus Saliba Monteiro; André Pegoraro Poor; Bruno Bracco Donatelli Muro; Caroline Veloso; Flávio de Aguiar Coelho; Rafaella Fernandes Carnevale; Francisco Alves Pereira; Fernanda Mariane dos Santos; et al. (Veterinary Research Communications, 2025)

Phosphate solubilization by filamentous fungi from Antarctic lichens and sediments - Adriely Vital de Souza Silva; Averlane Vieira da Silva; Adeildo Júnior de Oliveira; Rafaela Ferreira da Silva Costa; Rodrigo Paidano Alves; Luiz Henrique Rosa; Valéria Maia de Oliveira; Marcela Eugênia da Silva Cáceres; Janice Gomes Cavalcante; Sabrina Barros Cavalcante; Michel Rodrigo Zambrano Passarini; Aline Cavalcanti de Queiroz; et al. (Extremophiles, 2025)

Droughts, livestock expansion, and Forest degradation: A 37-year assessment of landscape change in a semiarid municipality of Brazil - Francisco Éder Rodrigues de Oliveira; Eveline de Almeida Ferreira; Rodrigo Fernandes; Victor Neudo Santos Tavares; Yara de Almeida Araújo; João Luiz Lima; Luiz Fernando de Sousa Antunes; Noely Raiana da Costa Chagas; Pedro Lucas Nogueira de Freitas; Cirley Tavares Lemos; Ayslan do Nascimento Fernandes; Eulene Francisco da Silva (Science of The Total Environment, 2025)

Decapod community composition is seasonally driven by different environmental factors in an estuarine-coastal gradient (Eastern Brazil) - Ronaldo R. Oliveira-Filho; Mariana Antunes; Joelson Musiello-Fernandes; Rodrigo Guéron; Helen Audrey Pichler; Ciro Colodetti Vilar; Fernando L. Mantelatto; Jean-Christophe Joyeux; Julien Chiquieri; Maurício Hostim-Silva; David Bauman (Regional Studies in Marine Science, 2025)

Entropy-Based Measure of Rock Sample Heterogeneity Derived from Micro-CT Images - Luan Coelho Vieira da Silva; Júlio de Castro Vargas Fernandes; Felipe Bevilaqua Foldes Guimarães; Pedro Henrique Braga Lisboa; Carlos Eduardo Menezes dos Anjos; Thais Fernandes de Matos; Marcelo Ramalho Albuquerque; Rodrigo Surmas; Alexandre Gonçalves Evsukoff (Transport in Porous Media, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Deep tillage improves the rhizosphere environment in rainfed coffee cultivation on dense Cambisols through plant-soil interaction - Pedro Antônio Namorato Benevenute; Fernandes Antônio Costa Pereira; Samara Martins Barbosa; Rodrigo Fonseca da Silva; Maila Adriely Silva; Gustavo Ferreira da Silva; Jucelino de Souza Lima; Leônidas Canuto Santos; Flávio Henrique Silveira Rabêlo; Aldir Carpes Marques Filho; Geraldo César de Oliveira; Bruno Montoani Silva (Rhizosphere, 2025)

Protected areas as hotspots of wildfire activity in fire-prone Temperate and Mediterranean biomes - Víctor Resco de Dios; Simon J. Schütze; Àngel Cunill Camprubí; Rodrigo Balaguer-Romano; Matthias M. Boer; Paulo M. Fernandes (Journal of Environmental Management, 2025)

Reintroduction of native species in an ecological restoration program from a quartzite area of campos rupestres - Aline Cristina Carvalho; Israel Marinho Pereira; Anderson Oliveira de Lima; José Cola Zanuncio; André Rodrigo Rech; Walisson Kenedy-Siqueira; Geraldo Wilson Fernandes (Plant and Soil, 2025)

Deep soil tillage in the coffee planting furrow has long-lasting benefits for improving soil physical quality and enhancing plant vigor in dense soils - Pedro Antônio Namorato Benevenute; Fernandes Antônio Costa Pereira; Samara Martins Barbosa; Rodrigo Fonseca da Silva; Mariany Isabela Soares Domingues; Aldir Carpes Marques Filho; Geraldo César de Oliveira; Bruno Montoani Silva (Soil and Tillage Research, 2025)

Associations among production systems, identity aspects, microbiological results and physical-chemical traits as revealed by official analyses of Minas Artisanal Cheese (QMA, Queijo Minas Artesanal) - Amanda Rosário Alvim Santos; Caio Fialho de Freitas; Anderson Carlos Camargo; Rafael Bombachi; Liliane Denize Miranda Menezes; Antônio Fernandes de Carvalho; Sergio Santos de Azevedo; Cinzia Caggia; Rodrigo Alves Barros; Luís Augusto Nero (Food Control, 2025)

Substitution of silage by soybean hulls in tropical forage-based dairy cow production system during the dry season - Jéssica Coutinho Mezzomo da Silva; Carlos Eduardo Avelino Cabral; Isis Scatolin de Oliveira; Alexandre Lima de Souza; Camila Fernandes Domingues Duarte; Rodrigo Schaurich Mativi Righi; Eduarda Caroline Kichel Cuff; Lucas Gimenes Mota; Carla Heloisa Avelino Cabral (Tropical Animal Health and Production, 2025)

Phenotypic and behavioral variation as a mechanism behind the invasive potential of a predatory neotropical fish - Marcos Ribeiro da Costa Gaspar; Angelo Antonio Agostinho; Paula Araújo Catelani; Rodrigo Fernandes; Ana Clara Sampaio Franco; José Luis Costa Novaes; Danielle Peretti; Ana Cristina Petry; Fernando Mayer Pelicice (Hydrobiologia, 2025)

Feeding rate for newly weaned tambaqui (Colossoma macropomum) juveniles in a recirculating aquaculture system - Bruno José Corecha Fernandes Eiras; Paola Fabiana Fazzi Gomes; Debora Sayumi Doami Melo; Jhonas Warlenson Palheta Nobre; Helen Cristiane Araújo Souza; Marcela Cardoso Sena; Joane Natividade; Igor Hamoy; Glauber David Almeida Palheta; Nuno Filipe Alves Correia de Melo; André Luiz Alves de Sá; Rodrigo Takata; et al. (Animal Feed Science and Technology, 2025)

Assessment of water and sediment quality in intermittent streams across different land uses in the Brazilian semiarid region: implications for sustainable irrigation and resource management - Yara de Almeida Araújo; Eveline de Almeida Ferreira; Rodrigo Fernandes; Gustavo Gonzaga Henry-Silva; Francisco Éder Rodrigues de Oliveira; Victor Neudo Santos Tavares; Jeane Cruz Portela; Marx Lima da Cunha; Noely Raiana da Costa Chagas; Luiz Fernando de Sousa Antunes; Antônio Gustavo de Luna Souto; Eulene Francisco da Silva (Environmental Science and Pollution Research, 2025)

Ovarian stimulation of Nelore calves and prepubertal heifers with a long-acting recombinant human FSH (corifollitropin-alpha) and subsequent ovum pick-up and in vitro embryo production outcomes - Rodrigo Moura; Carlos Antonio Fernandes; Luiz Gustavo Siqueira; Ricardo Alamino Figueiredo; Carlos Frederico Martins; Maurício Antonio Peixer; Marcelo Cunha Xavier; Joao Henrique Viana (Theriogenology, 2025)

Effects of the insecticide thiodicarb on non-target organs and behavior of the stingless bee Partamona helleri (Hymenoptera: Meliponini) - Davy Soares Gomes; Franciane Rosa Miranda; João Victor de Oliveira Motta; Mateus Soares de Oliveira; Cliver Fernandes Farder-Gomes; Daniel Silva Sena Bastos; Rodrigo Cupertino Bernardes; Fernanda Pereira da Silva; Pollyana Leão Gonçalves; Hugo Bolsoni Zago; Cynthia Canêdo da Silva; Leandro Licursi de Oliveira; et al. (Pesticide Biochemistry and Physiology, 2025)

In vitro study of essential oils encapsulated in chitosan microparticles against Histoplasma capsulatum and their pathogenicity in Caenorhabditis elegans - Anderson da Cunha Costa; Mirele Rodrigues Fernandes; Augusto Feynman Dias Nobre; Maria Gleiciane Rocha; Jacó Ricarte Lima de Mesquita; Rosemeyre Souza Freire; Andre Jalles Monteiro; Rodrigo Silveira Vieira; Raimunda Sâmia Nogueira Brilhante (Biofouling, 2025)

Can energy density influence treefrog distribution and species functional traits? - Ricardo Lourenço-de-Moraes; Amanda Lipinski Fernandes Maciel; Rodrigo Barbosa Ferreira; Evanilde Benedito (Evolutionary Ecology, 2025)

Estimation of genetic parameters for racing time and ranking in Thoroughbred horses - Denyus Augusto de Oliveira Padilha; Suelen Fernandes Padilha; Rafaela Martins; Bruna Elisa Machado Scheffer; Mayumi Regina Miliorini; Laila Talarico Dias; Rodrigo de Almeida Teixeira (Journal of Equine Veterinary Science, 2025)

Impression management in sustainability disclosures and information asymmetry: The case of Brazilian public companies - Alexandre Fernandes Monteiro; Rodrigo de Souza Gonçalves (Journal of Cleaner Production, 2025)

Can the supplementation of autolyzed yeast (Saccharomyces cerevisiae) affect the diet digestibility, feeding behavior, levels of blood metabolites, and performance of Dorper × Santa Ines lambs finished in feedlot? - Bruno Raphael Fasolli Schuh; Amauri Bernardi; Veridiana Lourenço Daley; Sergio Rodrigo Fernandes; José Antônio de Freitas (Tropical Animal Health and Production, 2025)

When a name changes everything: taxonomy and conservation of the Atlantic bushmaster ( Lachesis Daudin, 1803) (Serpentes: Viperidae: Crotalinae) - Breno Hamdan; Sandro L. Bonatto; Dennis Rödder; Victor Corrêa Seixas; Rogério Mercês Ferreira Santos; Diego José Santana; Larissa Gonçalves Machado; Jessica Matos Kleiz-Ferreira; Marco A. de Freitas; Rodrigo Castellari Gonzalez; Thabata Cavalcante; Moisés Barbosa de Souza; et al. (Systematics and Biodiversity, 2024)

Ship-shaped vessel hydroelastic numerically supported analysis in a narrow ultra-reduced model tank with full scale extrapolation - Antonio Carlos Fernandes; Rodrigo de Souza Silva; Filipe Salvador Lopes; Rodrigo Pinto de Castro; Joel Sena Sales Junior (Ocean Engineering, 2024)

Realized genetic gain with reciprocal recurrent selection in a Eucalyptus breeding program - Saulo F. S. Chaves; Luiz A. S. Dias; Rodrigo S. Alves; Filipe M. Ferreira; Maurício S. Araújo; Marcos D. V. Resende; Elizabete K. Takahashi; João E. Souza; Fernando P. Leite; Samuel B. Fernandes; Kaio Olimpio G. Dias (Tree Genetics & Genomes, 2024)

Isolation of marine-derived filamentous fungi and their potential application for bioremediation process - Osvaldo Manuel Núñez Nogueira; Suzan Prado Fernandes Bernal; Cleto Kaveski Peres; Marcela Boroski; Michel Rodrigo Zambrano Passarini (Brazilian Journal of Microbiology, 2024)

Ultrafast and high-throughput immunoassay assay to detect anti-SARS-CoV-2 IgG antibodies in dogs and cats - Ana Carolina Aparecida Gonçalves; Marcelo dos Santos Conzentino; Altina Bruna de Souza Barbosa; Fernando Rodrigo Doline; Mariana Guimarães Nilsson; Aristeu Vieira da Silva; Louise Bach Kmetiuk; Alexander Welker Biondo; Luciano Fernandes Huergo (Brazilian Journal of Microbiology, 2024)

Detection of virulent Klebsiella pneumoniae strains causing intestinal and extraintestinal infections during the 80s and 90s in Brazil - Tiago Barcelos Valiatti; Pedro Henrique Soares Nunes; Fernanda Fernandes Santos; Rodrigo Cayô; Ingrid Nayara Marcelino; Felipe Alberto-Lei; Haian Araujo Varjão; Ana Cristina Gales; Tânia Aparecida Tardelli Gomes (Brazilian Journal of Microbiology, 2024)

Enteroaggregative Escherichia coli (EAEC) isolates obtained from non-diarrheic children carry virulence factor-encoding genes from Extraintestinal Pathogenic E. Coli (ExPEC) - Bruna M. Luiz; Maria C. Cergole-Novella; Stéfani T. A. Dantas; Daiany R. P. de Lira; Guilherme F. R. de Souza; Iranildo do A. Fernandes; Henrique Orsi; Guilherme Solveira; Vera L. M. Rall; Luís F. dos Santos; Rodrigo T. Hernandes (Brazilian Journal of Microbiology, 2024)

Landscape and insecticide use affecting the Leucoptera coffeella infestation and the natural parasitism spatiotemporal distribution in brazilian coffee agroecosystems - Mateus Pereira dos Santos; Benício de Melo Santos Neto; Lilian Rocha Araújo; Ana Carolina Plácido Cardoso; Beatriz Sousa Coelho; Suzany Aguiar Leite; Aldenise Alves Moreira; Daniell Rodrigo Rodrigues Fernandes; Geraldo Andrade Carvalho; Maria Aparecida Castellani (Crop Protection, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

An ecological and evolutionary approach to arboreal communities under different environmental stress conditions - Carolina Njaime Mendes; Vanessa Leite Rezende; Ravi Fernandes Mariano; Cléber Rodrigo de Souza; Rubens Manoel dos Santos; Marco Aurélio Leite Fontes (Perspectives in Plant Ecology, Evolution and Systematics, 2024)

Biotechnological potential in agriculture of soil Antarctic microorganisms revealed by omics approach - Michel Rodrigo Zambrano Passarini; Marahia Isabel Guevara Robayo; Júlia Ronzella Ottoni; Alysson Wagner Fernandes Duarte; Luiz Henrique Rosa (World Journal of Microbiology and Biotechnology, 2024)

A New Species of Nealiolus Mason, 1974 (Hymenoptera: Braconidae) from Traditional Cocoa Agroforestry and Brazilian Atlantic Rainforest - Antonielson Bezerra Silva; José Victor Alves Ferreira; Maíra Benchimol; Eduardo Mitio Shimbori; Daniell Rodrigo Rodrigues Fernandes (Neotropical Entomology, 2024)

Disseminated paracoccidioidomycosis in a captive western black-handed tamarin (Saguinus niger) - Isabelle D. de Oliveira; Eduardo Ferreira-Machado; Jamile M. Garcia; Sarah R.J.S. Simões; Ketlyn B. Figueiredo; Rodrigo A. Ressio; André L.M. da Costa; Flora N. Matos; Cássia R.R. Gonzaga; Shamira S. Leandro; Marina A. de Medeiros; Rodrigo H.F. Teixeira; et al. (Journal of Comparative Pathology, 2024)

Global predictive invasion modeling of Asian wood-wasp Eriotremex formosanus (Matsumura) (Hymenoptera: Siricidae): insights gained from Pinus L. occurrences, and the first record of this invasive species in South America - Janderson Batista Rodrigues Alencar; Allan Clé Porto; Diego Dos Anjos Souza; Daniell Rodrigo Rodrigues Fernandes (Biological Invasions, 2024)

Impact assessment of IMO’s sulfur content limits: a case study at latin America’s largest grain port - Camila Arielle Bufato Moreira; Gabriela Polezer; Jéssica Caroline dos Santos Silva; Priscila Caroline de Souza Zorzenão; Ana Flavia Locateli Godoi; Luciano Fernandes Huergo; Carlos Itsuo Yamamoto; Yara de Souza Tadano; Sanja Potgieter-Vermaak; Rodrigo Arantes Reis; Andrea Oliveira; Ricardo Henrique Moreton Godoi (Air Quality, Atmosphere & Health, 2024)

Superovulating cattle with corifollitropin-alpha, a long-acting recombinant human FSH (rhFSH): Dose-response, half-life, effects on the ovaries, and embryo outcomes - Joao Henrique Moreira Viana; Rodrigo Martins de Moura; Leticia Prates Martins; Ricardo Alamino Figueiredo; Luiz Gustavo Bruno Siqueira; Carlos Antonio Carvalho Fernandes (Theriogenology, 2024)

Biological activities from açaí (Euterpe spp. Mart.) seeds and their pharmacological aspects: A systematic review and meta-analysis - Kaio Kelvin Barros Dias; Gabriel Araújo de Jesus; Ana Alice Farias da Costa; Fabíola Fernandes Costa; Geraldo Narciso da Rocha Filho; Rodrigo Juliano Oliveira; Renata Coelho Rodrigues Noronha; Luís Adriano Santos do Nascimento (PharmaNutrition, 2024)

Foreshadowing an exponential market: A brief story, applications, and perspectives of CRISPR/Cas system for the production of (hemi-)cellulases in filamentous fungi - Felipe Ferreira Silva; Natana Gontijo Rabelo; Klédna Constância Reis; Cássio Siqueira Souza Cassiano; Anderson Fernandes de Melo; Débora de Oliveira Lopes; Wagner Rodrigo de Souza; Marina Quádrio R.B. Rodrigues; Daniel Bonoto Gonçalves (Fungal Biology Reviews, 2024)

Exposure to the herbicide tebuthiuron affects behavior, enzymatic activity, morphology and physiology of the midgut of the stingless bee Partamona helleri - Cliver Fernandes Farder-Gomes; Franciane Rosa Miranda; Rodrigo Cupertino Bernardes; Daniel Silva Sena Bastos; Davy Soares Gomes; Fernanda Pereira da Silva; Pollyana Leão Gonçalves; Stella Arndt; André da Silva Xavier; Hugo Bolsoni Zago; José Eduardo Serrão; Gustavo Ferreira Martins; et al. (Environmental Toxicology and Pharmacology, 2024)

MYCOLICIBACTERIUM FORTUITUM INFECTION IN EX SITU EMERALD TREE BOA (Corallus batesii) - Cássia Regina Ramos Gonzaga; Flora Nogueira Matos; Mayara Grego Caiaffa; Maraya Lincoln Silva; Rodrigo Hidalgo Friciello Teixeira; Eduardo Ferreira-Machado; Ticiana Brasil Ervedosa; Pedro Enrique Navas-Suárez; Rodrigo Albergaria Ressio; Cinthya dos Santos Cirqueira; Ketlyn Bolsachini Figueiredo; Ana Carolina Souza Ramos de Carvalho; et al. (Brazilian Journal of Microbiology, 2024)

Water restriction alters seed bank traits and ecology in Atlantic Forest seasonal forests under climate change - Patrícia Borges Dias; Sustanis Horn Kunz; José Eduardo Macedo Pezzopane; Talita Miranda Teixeira Xavier; João Paulo Fernandes Zorzanelli; João Vitor Toledo; Lhoraynne Pereira Gomes; Rodrigo Gomes Gorsani (Global Change Biology, 2024)
The soil seed bank (SSB) is one of the key mechanisms that ensure the perpetuity of forests, but how will it behave in the scenarios projected for the future climate? Faced with this main question, still little explored in seasonal tropical forests, this study evaluated the germination, ecological attributes, and functional traits of the SSB in a seasonal forest in the Atlantic Forest. Forty‐eight composite samples of the SSB were collected from 12 plots, distributed across four treatments, each with 12 replicates. The samples were placed in two climate‐controlled greenhouses, establishing two environments of controlled climatic conditions, both with two levels of water, as follows: Cur: current scenario without water restriction; Cur_WR: current scenario with water restriction; RCP8.5: future scenario without water restriction; RCP8.5_WR: future scenario with water restriction. The germinants were identified, and their ecological attributes and functional traits were obtained. Leaf area and biomass production, differences in abundance, richness, and diversity were evaluated, along with analysis of variance to assess the interaction between water levels and scenarios. All ecological attributes and functional traits evaluated drastically decreased in the future projection with water restriction, with this restriction being the main component influencing this response. The increased temperature in the future scenario significantly raised water consumption compared to the current scenario. However, persistent water restrictions in the future could undermine the resilience of seasonal forests, hindering seed germination in the soil. Richness and abundance were also adversely affected by water scarcity in the future scenario, revealing a low tolerance to the projected prolonged drought. These changes found in the results could alter the overall structure of seasonal forests in the future, as well as result in the loss of the regeneration potential of the SSB due to decreased seed viability and increased seedling mortality.

Resistance training improves cardiac function in older women: a randomized controlled trial - Ricardo J. Rodrigues; Paolo M. Cunha; João P. Nunes; Lauro C. Vianna; Patrícia C. Brum; Danilo S. Bocalini; Andrei C. Sposito; Luis C. Miguita Junior; Max D. Oliveira; Elaine Batistella; Rodrigo R. Fernandes; Paulo S. Junior; et al. (GeroScience, 2024)

Processing parameters, techno-functional properties and potential food application of lentil protein concentrate as an ingredient for the plant-based market - Rodrigo Fernandes Caldeira; Lucas de Paiva Gouvêa; Tatiana de Lima Azevedo; Carmine Conte; Daniela de Grandi Castro Freitas de Sá; Melícia Cintia Galdeano; Ilana Felberg; Janice Ribeiro Lima; Caroline Grassi Mellinger (Food Research International, 2024)

Antarctic marine sediment as a source of filamentous fungi-derived antimicrobial and antitumor compounds of pharmaceutical interest - Karine Fernandes Camacho; Layssa de Melo Carlos; Suzan Prado Fernandes Bernal; Valéria M. de Oliveira; Jorge Luiz Maria Ruiz; Júlia Ronzella Ottoni; Rosemary Vieira; Arthur Neto; Luiz Henrique Rosa; Michel Rodrigo Zambrano Passarini (Extremophiles, 2024)

Tropical forest succession increases tree taxonomic and functional richness but decreases evenness - Masha T. van der Sande; Lourens Poorter; Géraldine Derroire; Mario Marcos do Espirito Santo; Madelon Lohbeck; Sandra C. Müller; Radika Bhaskar; Michiel van Breugel; Juan Manuel Dupuy‐Rada; Sandra M. Durán; Catarina C. Jakovac; Horacio Paz; et al. (Global Ecology and Biogeography, 2024)
Aim Successional changes in functional diversity provide insights into community assembly by indicating how species are filtered into local communities based on their traits. Here, we assess successional changes in taxonomic and functional richness, evenness and redundancy along gradients of climate, soil pH and forest cover. Location Neotropics. Time period Last 0–100 years. Major taxa studied Trees. Methods We used 22 forest chronosequence studies and 676 plots across the Neotropics to analyse successional changes in Hill's taxonomic and functional diversity of trees, and how these successional changes vary with continental‐scale gradients in precipitation, soil pH and surrounding forest cover. Results Taxonomic and functional richness and functional redundancy increased, while taxonomic and functional evenness decreased over time. Functional richness and evenness changed strongly when not accounting for taxonomic richness, but changed more weakly after statistically accounting for taxonomic richness, indicating that changes in functional diversity are largely driven by taxonomic richness. Nevertheless, the successional increases in functional richness when correcting for taxonomic richness may indicate that environmental heterogeneity and limiting similarity increase during succession. The taxonomically‐independent successional decreases in functional evenness may indicate that stronger filtering and competition select for dominant species with similar trait values, while many rare species and traits are added to the community. Such filtering and competition may also lead to increased functional redundancy. The changes in taxonomically‐independent functional diversity varied with resource availability and were stronger in harsh, resource‐poor environments, but weak in benign, productive environments. Hence, in resource‐poor environments, environmental filtering and facilitation are important, whereas in productive environments, weaker abiotic filtering allows for high initial functional diversity and weak successional changes. Main conclusion We found that taxonomic and functional richness and functional redundancy increased and taxonomic and functional evenness decreased during succession, mainly caused by the increasing number of rare species and traits due to the arrival of new species and due to changing (a)biotic filters.

Dynamics of dissolved inorganic carbon (DIC) and stable C isotope ratios (δ13CDIC) in a tropical watershed with diversified land use in São Paulo State, Brazil - Fabiano Tomazini da Conceição; Alexandre Martins Fernandes; Rodrigo Braga Moruzzi; Jefferson Mortatti (Science of The Total Environment, 2024)

An automated mineralogy derived criterion for clustering ore samples for mineral liberation studies - Rodrigo Fina Ferreira; Rosa Malena Fernandes Lima (Minerals Engineering, 2024)

Exposure to low-concentration fipronil impairs survival, behavior, midgut morphology and physiology of Aedes aegypti larvae - Cliver Fernandes Farder-Gomes; Franciane Rosa Miranda; Kenner Morais Fernandes; Rodrigo Cupertino Bernardes; Daniel Silva Sena Bastos; Leandro Licursi de Oliveira; Gustavo Ferreira Martins; José Eduardo Serrão (Chemosphere, 2024)

Unveiling novel threats: Urban river isolation of Aeromonas veronii with unusual VEB-28 extended-spectrum β-lactamase and distinct mcr variants - Fernanda Fernandes Santos; Tiago Barcelos Valiatti; André Valêncio; Ághata Cardoso da Silva Ribeiro; Ana Paula Streling; Tânia A. Tardelli Gomes; Rodrigo Cayô; Ana Cristina Gales (Chemosphere, 2024)

Genetic parameters for mesenteric torsion in a pig maternal line - Suelen Fernandes Padilha; Amauri Felipe Evangelista; Luis Orlando Duitama Carreño; Marcelo Silva Freitas; Jader Silva Lopes; Adriana Mércia Guaratini Ibelli; Jane de Oliveira Peixoto; Marcos Antônio Zanella Morés; Maurício Egídio Cantão; Mônica Corrêa Ledur; Rodrigo de Almeida Teixeira; Laila Talarico Dias (Livestock Science, 2024)

Co-resistance to methicillin and clindamycin among coagulase-negative staphylococci isolates recovered from pet food in Brazil - Ikechukwu Benjamin Moses; Ingrid Nayara Marcelino Santos; Ághata Cardoso da Silva Ribeiro; Fernanda Fernandes Santos; Rodrigo Cayô; Ana Cristina Gales (International Journal of Food Microbiology, 2024)

Lactobacillus delbrueckii CIDCA 133 fermented milk modulates inflammation and gut microbiota to alleviate acute colitis - Luís Cláudio Lima de Jesus; Andria dos Santos Freitas; Joyce da Cruz Ferraz Dutra; Gabriela Munis Campos; Monique Ferrary Américo; Juliana Guimarães Laguna; Evandro Gonçalves Dornelas; Rodrigo Dias de Oliveira Carvalho; Kátia Duarte Vital; Simone Odília Antunes Fernandes; Valbert Nascimento Cardoso; Jamil Silvano de Oliveira; et al. (Food Research International, 2024)

Biochar Mitigates the Harmful Effects of Drought in Soybean Through Changes in Leaf Development, Stomatal Regulation, and Gas Exchange - Maria Andressa Fernandes Gonçalves; Breno Ricardo Serrão da Silva; João Rodrigo Coimbra Nobre; Bruno Lemos Batista; Allan Klynger da Silva Lobato (Journal of Soil Science and Plant Nutrition, 2024)

Fishing and recording dead fish by citizen scientists contribute valuable data on south American ray-finned fish diversity - Lucas Rodriguez Forti; José Luís Costa Novaes; Milena Wachlevski; Rodrigo Silva da Costa; Jandson Lucas Camelo da Silva; Juan Lima; Adriana Maria Alves; Lorena B. Thaíza Fernandes; Judit K. Szabo (Biodiversity and Conservation, 2024)

Aflatoxins and fumonisins in conventional and organic corn: a comprehensive review - Amanda L. Gomes; Rodrigo R. Petrus; Ricardo L. M. de Sousa; Andrezza M. Fernandes (Food Additives & Contaminants: Part A, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Evolutionary fingerprint, phylogenetic and forest structure of tropical montane Atlantic cloud forests along an elevation gradient - Ravi Fernandes Mariano; Vanessa Leite Rezende; Cléber Rodrigo de Souza; Patrícia Vieira Pompeu; Rubens Manoel dos Santos; Carolina Njaime Mendes; Aloysio Souza de Moura; Felipe Santana Machado; Warley Augusto Caldas Carvalho; Marco Aurélio Leite Fontes (Journal of Mountain Science, 2024)

Toxicity Assessment of the Biogenic Amines Cadaverine and Putrescine in Aquatic Organisms - Ana Paula Andrade Braga; José Henrique Vallim; Rodrigo Fernandes Castanha; Vera Lucia Scherholz Salgado de Castro; Maria Aparecida Marin-Morales (Water, Air, & Soil Pollution, 2024)

Comparative craniometric analysis between two species of South American canids and domestic dogs - Rodrigo Antonio Fernandes; Isabelle Leite Miam; Guilherme da Silva Rogério; Luciana Del Rio Pinoti; Fabiano Antonio Cadioli; Yuri Tani Utsunomiya (Journal of Mammalian Evolution, 2024)

Low doses of malathion impair ovarian, uterine, and follicular integrity by altering oxidative profile and gene expression of rats exposed during the peripubertal period - Rafaela Pires Erthal-Michelato; Giovanna Fachetti Frigoli; Ariana Musa de Aquino; Ana Paula Franco Punhagui-Umbelino; Wellerson Rodrigo Scarano; Glaura Scantamburlo Alves Fernandes (Environmental Science and Pollution Research, 2024)

Exploring the potential of tannin-rich tree bark extracts in combating foodborne diseases and gastric cancer - João Gilberto Meza Ucella-Filho; Mario Sérgio Lorenço; Bruna Rafaella Ferreira da Silva; Vanuzia Rodrigues Fernandes Ferreira; Jessica Raquel Borges Monteiro; Nicolly Soares Ferreira; Maria das Graças Cardoso; Rodrigo Rezende Kitagawa; Juliana Alves Resende; Ananias Francisco Dias Junior; Roberta Hilsdorf Piccoli; Fábio Akira Mori (Food Bioscience, 2024)

Essential Oil from Pimenta pseudocaryophyllus (Myrtaceae) Leaves and Its Major Compounds Against the Mexican Bean Weevil - Leandro do Prado Ribeiro; Rodrigo Donizeti Faria; Edenilson dos Santos Niculau; Gabriel Luiz Padoan Gonçalves; Thiago Felipe Ansante; Maria Fátima das Graças Fernandes da Silva; José Djair Vendramim (Journal of Crop Health, 2024)

The end of an entire biome? World's largest wetland, the Pantanal, is menaced by the Hidrovia project which is uncertain to sustainably support large-scale navigation - Karl M. Wantzen; Mario Luis Assine; Ieda Maria Bortolotto; Debora Fernandes Calheiros; Zilca Campos; Agostinho Carlos Catella; Rafael Morais Chiaravalotti; Walter Collischonn; Eduardo Guimarães Couto; Catia Nunes da Cunha; Geraldo Alves Damasceno-Junior; Carolina Joana da Silva; et al. (Science of The Total Environment, 2024)

Do tides equally influence the reproductive cycle of two symbiotic estuarine shrimp? - Rodrigo Guéron; Douglas Fernandes Rodrigues Alves; Alexandre Oliveira Almeida (Regional Studies in Marine Science, 2023)

Kombucha based on unconventional parts of the Hibiscus sabdariffa L.: Microbiological, physico-chemical, antioxidant activity, cytotoxicity and sensorial characteristics - Gislane Romano Mendonça; Rodrigo Anacleto Pinto; Érika Almeida Praxedes; Virgínia Kelly Gonçalves Abreu; Richard Pereira Dutra; Alexsandra Fernandes Pereira; Tatiana de Oliveira Lemos; Aramys Silva dos Reis; Ana Lúcia Fernandes Pereira (International Journal of Gastronomy and Food Science, 2023)

Integrated planning of forest exploration infrastructures in an amazonian sustainable forest management area - Marcelo Otone Aguiar; Gilson Fernandes da Silva; Geraldo Regis Mauri; Adriano Ribeiro de Mendonça; Evandro Ferreira da Silva; Evandro Orfano Figueiredo; Jeferson Pereira Martins Silva; Valéria Alves da Silva; Rodrigo Freitas Silva; Gabriel Lessa Lavagnoli (Forest Ecology and Management, 2023)

Neglected bacterial infections associated to bovine respiratory disease in lactating cows from high-yielding dairy cattle herds - Rodrigo Pelisson Massi; Michele Lunardi; Alice Fernandes Alfieri; Amauri Alcindo Alfieri (Brazilian Journal of Microbiology, 2023)

How natural and anthropogenic factors should drive microplastic behavior and fate: The scenario of Brazilian urban freshwater - Fernando F. Sodré; Imisi M. Arowojolu; Maria C. Canela; Rodrigo S. Ferreira; Andreia N. Fernandes; Cassiana C. Montagner; Cristiane Vidal; Mariana A. Dias; Gilberto Abate; Leticia C. da Silva; Marco T. Grassi; Crislaine Bertoldi; et al. (Chemosphere, 2023)

WITHDRAWN: Marine intrusions drive short-term and long lasting changes on limnological dynamics along the water column of a tropical coastal lagoon - Jorge Gabriel Fernandes Genovez; Théo Dias Arueira; Luís Alfredo dos Santos Prado; Giovanna Figueiredo Lima da Silva; Claudio Cardoso Marinho; André Luiz dos Santos Fonseca; Murilo Minello; Daniel Basílio Zandonadi; Rodrigo Lemes Martins; Francisco de Assis Esteves; Anderson da Rocha Gripp (Limnologica, 2023)

A novel strategy to predict clonal composites by jointly modeling spatial variation and genetic competition - Filipe M. Ferreira; Saulo F.S. Chaves; Leonardo L. Bhering; Rodrigo S. Alves; Elizabete K. Takahashi; João E. Sousa; Marcos D.V. Resende; Fernando P. Leite; Salvador A. Gezan; José M.S. Viana; Samuel B. Fernandes; Kaio O.G. Dias (Forest Ecology and Management, 2023)

Lipidomic analysis identified potential predictive biomarkers of statin response in subjects with Familial hypercholesterolemia - Alvaro Cerda; Raul Hernandes Bortolin; Marcos Yukio Yoshinaga; Renata Caroline Costa de Freitas; Carolina Dagli-Hernandez; Jessica Bassani Borges; Victor Fernandes de Oliveira; Rodrigo Marques Gonçalves; Andre Arpad Faludi; Gisele Medeiros Bastos; Rosario Dominguez Crespo Hirata; Mario Hiroyuki Hirata (Chemistry and Physics of Lipids, 2023)

LDLR and PCSK9 3´UTR variants and their putative effects on microRNA molecular interactions in familial hypercholesterolemia: a computational approach - Renata Caroline Costa de Freitas; Raul Hernandes Bortolin; Jessica Bassani Borges; Victor Fernandes de Oliveira; Carolina Dagli-Hernandez; Elisangela da Silva Rodrigues Marçal; Gisele Medeiros Bastos; Rodrigo Marques Gonçalves; Andre Arpad Faludi; Vivian Nogueira Silbiger; André Ducati Luchessi; Rosario Dominguez Crespo Hirata; et al. (Molecular Biology Reports, 2023)

Fermentative parameters and chemical composition of mixed silages from corn-crotalaria intercropping - Carolina M. Costa Araujo; Edgar S. Jara Galeano; Marco A.P. Orrico Junior; Tatiane Fernandes; Joyce P. Alves; Marciana Retore; Mabio S.J. Silva; Ana C.A. Orrico; Rodrigo A. Garcia; Luis A.Z. Machado (Animal Feed Science and Technology, 2023)

Nutrient cycling aspects as possible ecosystem functional indicators of successional stage in Semideciduous seasonal forest, Rio de Janeiro state, Brazil - Rodrigo Camara de Souza; Marcos Gervasio Pereira; Deivid Lopes Machado; Luciano de Oliveira Toledo; Carlos Eduardo Gabriel Menezes; Gilsonley Lopes dos Santos; Fernando Silva Coutinho; Roni Fernandes Guareschi; Victória Maria Monteiro Mendonça (Acta Oecologica, 2023)

Imidacloprid: Impact on Africanized Apis mellifera L. (Hymenoptera: Apidae) workers and honey contamination - Cristiane Lurdes Paloschi; Maria Hermínia Ferreira Tavares; Elizabeth Artus Berte; Kathleen Model; Karine Medina Rosa; Fagner Goes da Conceição; Fernanda Raulino Domanski; Edgar de Souza Vismara; Paula Fernandes Montanher; Rodrigo Mendes Antunes Maciel; Leticia da Silva Ribeiro; Natalia Ramos Mertz; et al. (Chemosphere, 2023)

Spray-chilling system in the initial cooling process of swine half carcasses - Alessandra Pereira dos Santos; Fabiana Ribeiro Caldara; Alexandre Rodrigo Mendes Fernandes; Maria Fernanda de Castro Burbarelli; Bruna de Souza Eberhart; Jean Kaique Valentim; Ibiara Correia de Lima Almeida Paz; Rodrigo Garófallo Garcia; Agnês Markiy Odakura (Meat Science, 2023)

Geochemistry and geochronology of the Imbicuí Complex, Western Dom Feliciano Belt, Brazil: Tonian adakite-like subduction-related rocks - Rosemeri Soares Siviero; Edinei Koester; Luis Alberto Dávila Fernandes; Delphine Bosch; Olivier Bruguier; Daniel Triboli Vieira; Rodrigo Chaves Ramos; Gustavo Kraemer (Journal of South American Earth Sciences, 2023)

Ecotoxicity studies of two atrazine nanoformulations: From the evaluation of stability in media to the effects on aquatic organisms - Rodrigo Fernandes Castanha; Anderson do Espírito Santo Pereira; Gabriela Patricia Unigarro Villarreal; José Henrique Vallim; Fernanda Sana Pertrini; Claudio Martín Jonsson; Leonardo Fernandes Fraceto; Vera Lúcia Scherholz Salgado de Castro (Environmental Pollution, 2023)

Unintended consequences of valuing the contributions of non-native species: misguided conservation initiatives in a megadiverse region - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Carlos Bernardo Mascarenhas Alves; Marlene Sofia Arcifa; Valter M. Azevedo-Santos; Marcelo Fulgêncio Guedes Brito; Pâmella Silva de Brito; Paula Maria Gênova de Castro Campanha; Fernando Rogério Carvalho; Gabriel Costa da Costa; Mario Alberto Cozzuol; Almir Manoel Cunico; et al. (Biodiversity and Conservation, 2023)

Behavior of deteriogenic fungi in aviation fuels (fossil and biofuel) during simulated storage - Mariane Rodrigues Lobato; Juciana Clarice Cazarolli; Regiane Débora Fernandes Rios; Emmanuel Bezerra D’ Alessandro; Marcia T. S Lutterbach; Nelson Roberto Antoniosi Filho; Vânya Márcia Duarte Pasa; Donato Aranda; Pedro Rodrigo Scorza; Fátima Menezes Bento (Brazilian Journal of Microbiology, 2023)

Macroalgal diversity along an environmental gradient in a saltwork - Rodrigo Herico Rodrigues de Melo Soares; Felipe de Oliveira Fernandes; Ciro Anizio de Assunção; Henrique D.S. Borburema; Marcella Araújo do Amaral Carneiro; Eliane Marinho-Soriano (Estuarine, Coastal and Shelf Science, 2023)

Shading effect and forage production of tropical grasses in Brazilian semi-arid silvopastoral systems - Clemente Fernandes dos Santos Neto; Rodrigo Gregório da Silva; Samuel Rocha Maranhão; Ana Clara Rodrigues Cavalcante; Vitor Hugo Maues Macedo; Magno José Duarte Cândido (Agroforestry Systems, 2023)

The prokaryotic community of Chondrosia reniformis Nardo, 1847: from diversity to mercury detection - Camilla Roveta; Barbara Calcinai; Federico Girolametti; Joana Fernandes Couceiro; Stefania Puce; Anna Annibaldi; Rodrigo Costa (Zoology, 2023)

Conditioned medium of mesenchymal stem cells: application in mares with endometrial fibrosis - Fabiano Trevisan da Rocha; Janislene Mach Trentin; Henrique Boll de Araújo Bastos; Rômulo Oliveira Fernandes da Silva; Matheus Souto de Freitas; Rodrigo Costa Mattos; Nélson Alexandre Kreztmann Filho; Mara Iolanda Batistella Rubin (Journal of Equine Veterinary Science, 2023)

Effect of adding different types of soluble fibre to high-protein yoghurts on water holding capacity, particle size distribution, apparent viscosity, and microstructure - Elisângela Ramieres Gomes; Caroline Barroso dos Anjos Pinto; Rodrigo Stephani; Antônio Fernandes de Carvalho; Ítalo Tuler Perrone (International Dairy Journal, 2023)

Sensor validation to record rumination and analysis of behavioral parameters of dairy Gyr heifers in feedlot systems - Ricardo Davi Kliemann; Sergio Rodrigo Fernandes; Mariana Magalhães Campos; Thierry Ribeiro Tomich; Luiz Gustavo Ribeiro Pereira; Américo Fróes Garcez Neto (Tropical Animal Health and Production, 2023)

Antifungal and antiparasitic activity of Wunderlichia azulensis (Asteraceae) roots - Fernanda Gomes Trindade; Gabriel Bonan Taveira; Laís Pessanha de Carvalho; Vinícius Fernandes Moreira; Rodrigo Barbosa Braga Feitoza; Valdirene Moreira Gomes; Ivo José Curcino Vieira; Raimundo Braz-Filho; Edésio José Tenório de Melo; Maura Da Cunha (Plant Biosystems, 2023)

A systematic review of the toxic effects of a nanopesticide on non-target organisms: Estimation of protective concentrations using a species sensitivity distribution (SSD) approach – The case of atrazine - Thuanne Braúlio Hennig; Felipe Ogliari Bandeira; Rodrigo Costa Puerari; Leonardo Fernandes Fraceto; William Gerson Matias (Science of The Total Environment, 2023)

Daily variability of pelagic metabolism in a subtropical lagoonal estuary - Luís Henrique Bordin; Eunice Da C. Machado; Carlos R.B. Mendes; Elisa H.L. Fernandes; Maurício G. Camargo; Rodrigo Kerr; Carlos A. Schettini (Journal of Marine Systems, 2023)

A new insight about the selection and intake of forage by ewes and lambs in different production systems on pasture - Laura Derenevicz Faisca; Mylena Taborda Piquera Peres; Sergio Rodrigo Fernandes; Olivier Jean François Bonnet; Rafael Batista; Leonardo Deiss; Alda Lúcia Gomes Monteiro (Small Ruminant Research, 2023)

Association of Fructo-oligosaccharides and Arginine Improves Severity of Mucositis and Modulate the Intestinal Microbiota - Maria Emília Rabelo Andrade; Luisa Martins Trindade; Paola Caroline Lacerda Leocádio; Jacqueline Isaura Alvarez Leite; Diego Carlos dos Reis; Geovanni Dantas Cassali; Tales Fernando da Silva; Rodrigo Dias de Oliveira Carvalho; Vasco Ariston de Carvalho Azevedo; Gregório Grama Cavalcante; Jamil Silvano de Oliveira; Simone Odília Antunes Fernandes; et al. (Probiotics and Antimicrobial Proteins, 2023)

Paraprobiotics strains accelerate wound repair by stimulating re-epithelialization of NIH-3T3 cells, decreasing inflammatory response and oxidative stress - Monique Michels; Emily Córneo; Luana Bezerra Gonçalves Rocha; Rodrigo Dias; Ana Paula Lorenzen Voytena; Marina Rossetto; Fernanda Ramlov; Felipe Dal-Pizzol; Gabriel Fernandes Alves Jesus (Archives of Microbiology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Applicability of machine learning techniques in food intake assessment: A systematic review - Larissa Oliveira Chaves; Ana Luiza Gomes Domingos; Daniel Louzada Fernandes; Fabio Ribeiro Cerqueira; Rodrigo Siqueira-Batista; Josefina Bressan (Critical Reviews in Food Science and Nutrition, 2023)

Structural model and features of the world-class Cuiabá orogenic gold deposit, Rio das Velhas greenstone belt, Quadrilátero Ferrífero region, Brazil - Raphael do Carmo Fernandes; Jorge Roncato; Rodrigo Sérgio de Paula (Journal of South American Earth Sciences, 2023)

Genome-Based Characterization of Multidrug-Resistant Escherichia coli Isolated from Clinical Bovine Mastitis - Taila dos Santos Alves; Vinícius Sanches Rosa; Domingos da Silva Leite; Simony Trevizan Guerra; Sâmea Fernandes Joaquim; Felipe Freitas Guimarães; José Carlos de Figueiredo Pantoja; Simoni Baldini Lucheis; Vera Lúcia Mores Rall; Rodrigo Tavanelli Hernandes; Helio Langoni; Márcio Garcia Ribeiro (Current Microbiology, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Canine distemper virus and canine adenovirus type 1 co-infection in a free-living hoary fox (Lycalopex vetulus) from Brazil - Maraya Lincoln Silva; Mayara Grego Caiaffa; André Luiz Mota da Costa; Rodrigo Hidalgo Friciello Teixeira; Ticiana Brasil Ervedosa; Eduardo Ferreira Machado; Pedro Enrique Navas Suárez; Rodrigo Albergaria Réssio; Cinthya Cirqueira Borges; Isis Paixão de Jesus; Julia de Carvalho; Ketlyn Bolsachini Figueiredo; et al. (Brazilian Journal of Microbiology, 2023)

Drivers and implications of the extreme 2022 wildfire season in Southwest Europe - Marcos Rodrigues; Àngel Cunill Camprubí; Rodrigo Balaguer-Romano; Celso J. Coco Megía; Francisco Castañares; Julien Ruffault; Paulo M. Fernandes; Víctor Resco de Dios (Science of The Total Environment, 2023)

Ecological risk assessment of metal and hydrocarbon pollution in sediments from an urban tropical estuary: Tijuca lagoon (Rio de Janeiro, Brazil) - Matheus Teixeira; Ricardo Cesar; Denis Abessa; Celeste Siqueira; Rodrigo Lourenço; Mariana Vezzone; Yan Fernandes; Gustavo Koifman; Fernando Cesar Perina; Roberto Meigikos dos Anjos; Helena Polivanov; Zuleica Castilhos (Environmental Science and Pollution Research, 2023)

Morphological characteristics and yield of Opuntia stricta and Nopalea cochenillifera in integrated crop systems with caatinga trees - Clemente Fernandes dos Santos Neto; Rodrigo Gregório da Silva; Samuel Rocha Maranhão; Cleber Medeiros Barreto; Marcos Neves Lopes; Magno José Duarte Cândido (Agroforestry Systems, 2023)

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Acute and chronic effects of physical exercise on IgA and IgG levels and susceptibility to upper respiratory tract infections: a systematic review and meta-analysis - Lucas Rios Drummond; Helton Oliveira Campos; Filipe Rios Drummond; Gabriel Moraes de Oliveira; João Guilhermo Rios Pimenta Fernandes; Rodrigo Prates Amorim; Mateus da Costa Monteiro; Henrique Fernandes Gerspacher Lara; Laura Hora Rios Leite; Cândido Celso Coimbra (Pflügers Archiv - European Journal of Physiology, 2022)

Fipronil exposure compromises respiration and damages the Malpighian tubules of the stingless bee Partamona helleri Friese (Hymenoptera: Apidae) - Cliver Fernandes Farder-Gomes; Abraão Almeida Santos; Kenner Morais Fernandes; Rodrigo Cupertino Bernardes; Gustavo Ferreira Martins; José Eduardo Serrão (Environmental Science and Pollution Research, 2022)

Diagnosis and successful treatment of Brazillian porcupine poxvirus infection in a free-ranging hairy dwarf porcupine (Coendu spinosus) - Juliana Mariotti Guerra; Pedro Enrique Navas-Suárez; Eduardo Ferreira-Machado; Ticiana Brasil Ervedosa; Ketlyn Bolsachini Figueiredo; Ana Carolina Souza Ramos de Carvalho; Maraya Lincoln Silva; Mayara Grego Caiaffa; André Luiz Mota da Costa; Rodrigo Hidalgo Friciello Teixeira; Thais Eleonora Madeira Buti; Adriana Luchs; et al. (Brazilian Journal of Microbiology, 2022)

Does the same refuge signify the same reproductive tactics? Comparing the mating systems of two symbiont alpheid shrimps (Crustacea: Decapoda) - Rodrigo Guéron; Douglas Fernandes Rodrigues Alves; José Roberto Botelho de Souza; Alexandre Oliveira Almeida (Marine Ecology, 2022)
Animal populations can present different mating tactics according to the number of mates males or females obtain. The limiting factors for copulation in symbiont crustaceans are the size, structural complexity, and density of refuge, in addition to predation risk outside their shelters. In this study, we aimed to investigate, comparatively, if the occupation of the same refuge leads to the same reproductive tactic in two symbiont species of alpheid shrimps. For this purpose, we described the population distribution of Alpheus estuariensis , a burrowing shrimp, and Salmoneus carvachoi , a tenant species, in an intertidal mudflat in Pernambuco, northeastern Brazil. Alpheus estuariensis experiences sexual dimorphism relative to body and cheliped size, where males present larger body sizes and allocate more resources to cheliped growth than females. However, both males and females presented positive allometric growth in chelipeds. In S. carvachoi , male‐phase individuals reach smaller body sizes than hermaphrodites. Male‐phase shrimps experience positive allometry in cheliped size, while hermaphrodites do not. Both species were found inhabiting burrows as sexual pairs more frequently than expected by chance. Paired females of A. estuariensis were found carrying embryos more frequently than solitary ones. We did not find a statistical difference between the frequency of single and paired ovigerous hermaphrodites in S. carvachoi . Our results indicate that A. estuariensis is social monogamous, while S. carvachoi is promiscuous. We argue that different biological and ecological aspects of these species could explain the distinct tactics adopted by them. Alpheus estuariensis digs its own refuge and is a much larger species, bearing a more robust cheliped than S. carvachoi . Thus, we argue that the burrowing species ( A. estuariensis ) should monopolize and defend their refuge, and S. carvachoi only takes advantage of this resource.

Investigation of avian rotavirus infections in broiler chicks from commercial flocks with different performance efficiency indexes - Jéssica Cristhine Gallego; Daniela Lorencena; Janaína Lustosa de Mello; Ruana Renostro Delai; Mônica Regina de Matos; Aline de Marco Viott; Elis Lorenzetti; Amauri Alcindo Alfieri; Sergio Rodrigo Fernandes; Elisabete Takiuchi (Veterinary Research Communications, 2022)

A fatal case of dengue hemorrhagic fever associated with dengue virus 4 (DENV-4) in Brazil: genomic and histopathological findings - Mariana Sequetin Cunha; Thaís de Moura Coletti; Juliana Mariotti Guerra; César Cliento Ponce; Natalia Coelho Couto Azevedo Fernandes; Rodrigo Albegaria Résio; Ingra Morales Claro; Flávia Salles; Daniel Ferreira Lima Neto; Ester Sabino (Brazilian Journal of Microbiology, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

The industrial versatility of Gluconobacter oxydans: current applications and future perspectives - Gabrielle Alves Ribeiro da Silva; Simone Santos de Sousa Oliveira; Sara Fernandes Lima; Rodrigo Pires do Nascimento; Andrea Regina de Souza Baptista; Sorele Batista Fiaux (World Journal of Microbiology and Biotechnology, 2022)

Metabolic Profile of the Soil Microbial Community Exposed to Arsenite and Arsenate: a 1-Year Experiment - Rodrigo de Lima Brum; Lisiane Martins Volcão; Livia da Silva Freitas; Jessica El Koury Santos; Mariana Vieira Coronas; Juliane Ventura-Lima; Daiane Dias; Bruno Meira Soares; Erico Kunde Corrêa; Ng Haig They; Daniela Fernandes Ramos; Flavio Manoel Rodrigues da Silva Júnior (Water, Air, & Soil Pollution, 2022)

Effects of different probiotic strains B. lactis, L. rhamnosus and L. reuteri on brain-intestinal axis immunomodulation in an endotoxin-induced inflammation - Monique Michels; Gabriel Fernandes Alves Jesus; Mariane Rocha Abatti; Emily Córneo; Luana Cucker; Heloisa de Medeiros Borges; Natan da Silva Matos; Luana Bezerra Rocha; Rodrigo Dias; Carla Sasso Simon; Ana Paula Lorenzen Voytena; Marina Rossetto; et al. (Molecular Neurobiology, 2022)

New record of the bat falcon (Falco rufigularis) in northeastern Brazil: Implications for its future distribution under climate change - Maria Eduarda Alves Ferreira; Rodrigo Ferraz Jardim Marques; Hélio Francisco Leite; Alexandre M. Fernandes (Biologia, 2022)

A Promising Approach to Mitigate Risks on the Existing Tailings Dams in Brazil - José Tavares Araruna; Ronald Mejia Sanchez; Xuejiao Qi; Hongtao Wang; Shuguang Liu; Rodrigo Fernandes Magalhães de Souza; Paola Machado Barreto Manhães (Bulletin of Environmental Contamination and Toxicology, 2022)

Framework for Improving Land Boundary Conditions in Ocean Regional Products - Francisco Campuzano; Flávio Santos; Lucian Simionesei; Ana R. Oliveira; Estrella Olmedo; Antonio Turiel; Rodrigo Fernandes; David Brito; Marco Alba; Antonio Novellino; Ramiro Neves (Journal of Marine Science and Engineering, 2022)
The coupling of coastal or regional ocean models to hydrological models or observed data is currently an uncommon practice in operational oceanography. Though hydrological models are regarded as a powerful and useful tool for estimating the quantity and quality of freshwater running in a watershed, they fail to provide accurate results for river flow reaching the coastal area due to water-management activities occurring within the river catchment, activities such as human consumption, irrigation, storage, etc. For this reason, many coastal and regional ocean models continue to impose surface zero-salinity discharges as land boundary conditions for representing such a dynamic boundary. Moreover, river flows are based in climatologies, thus neglecting seasonal and interannual variability. To achieve those objectives, this study proposes an integrated methodology ranging from watershed models to validation in the coastal area and passing through methods and proxies for integrating the freshwater flows into regional ocean models. The main objective of this study is to explore the results obtained by using more sophisticated land boundary conditions based on the capacities of state-of-the-art hydrologic models combined with observation networks. In addition to the evaluation of the source of river-flow data, this work also explores the use of estuarine proxies based on simple modelling grids. The estuarine proxies enable the incorporation of the mixing processes that take place in estuaries into the land fluxes and obtain the plume momentum. The watershed, estuarine proxies, and ocean were modelled using the MOHID Water modelling system and evaluated in western Iberia waters. The modelling results served to illustrate the sea surface salinity extension of the Western Iberia Buoyant Plume (WIBP) during an extreme event in March 2018.

Spread of multidrug-resistant Acinetobacter baumannii isolates belonging to IC1 and IC5 major clones in Rondônia state - Tiago Barcelos Valiatti; Tatiane Silva Carvalho; Fernanda Fernandes Santos; Carolina Silva Nodari; Rodrigo Cayô; Juliana Thalita Paulino da Silva; Cicileia Correia da Silva; Jacqueline Andrade Ferreira; Lorena Brandhuber Moura; Levy Assis dos Santos; Ana Cristina Gales (Brazilian Journal of Microbiology, 2022)

Decreased susceptibility to imipenem and ceftazidime in early virulent Raoultella spp. strains retrieved from human intestinal infections - Tiago Barcelos Valiatti; Fernanda Fernandes Santos; Pedro Henrique Soares Nunes; Ana Paula Streling; Ruanita Veiga; Rodrigo Cayô; Ana Cristina Gales; Tânia Aparecida Tardelli Gomes (Brazilian Journal of Microbiology, 2022)

Cultured and uncultured microbial community associated with biogas production in anaerobic digestion processes - Júlia Ronzella Ottoni; Suzan Prado Fernandes Bernal; Tiago Joelzer Marteres; Franciele Natividade Luiz; Viviane Piccin dos Santos; Ângelo Gabriel Mari; Juliana Gaio Somer; Valéria Maia de Oliveira; Michel Rodrigo Zambrano Passarini (Archives of Microbiology, 2022)

Multilocus phylogeography of the endemic and endangered angular angelshark (Squatina guggenheim) in the Southwest Atlantic Ocean - Ingrid Vasconcellos Bunholi; Bruno Lopes da Silva Ferrette; Rodrigo Rodrigues Domingues; Matheus Marcos Rotundo; Juan Martín Cuevas; Mirta García; Sebastián Gómez; Renato Hajenius Aché de Freitas; Claudio Oliveira; Fausto Foresti; Fernando Fernandes Mendonça (Hydrobiologia, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

Microclimate and animal thermal comfort indexes in different silvopastoral system arrangements in Caatinga - Clemente Fernandes dos Santos Neto; Rodrigo Gregório da Silva; Samuel Rocha Maranhão; Antônia Flávia Fernandes Torres; José Antonio Delfino Barbosa Filho; Vitor Hugo Maués Macedo; Magno José Duarte Cândido (International Journal of Biometeorology, 2022)

Mercury chloride toxicity in juveniles Prochilodus argenteus a species from southeastern Brazil - Emília Tatiane Lopes da Silva; Marcelo Mattos Pedreira; Maria Letícia Fernandes Dias; Marcos Vinícius Teles Gomes; Marcus Alvarenga Soares; Rodrigo Sá Fortes Pedreira; Marianne Schorer (Environmental Science and Pollution Research, 2022)

Current Panorama, Practice Gaps, and Recommendations to Accelerate the Transition to a Circular Bioeconomy in Latin America and the Caribbean - Rodrigo Salvador; Reinalda Blanco Pereira; Gabriel Fernandes Sales; Vanessa Campana Vergani de Oliveira; Anthony Halog; Antonio C. De Francisco (Circular Economy and Sustainability, 2022)

Molecular genotyping reveals inter-regional relatedness among antimicrobial resistant Salmonella Minnesota strains isolated from poultry farm and humans, Brazil - João Paulo Fernandes Ferreira Moreira; Daniel Farias Marinho do Monte; Camila de Aguiar Lima; Celso José Bruno de Oliveira; Nelson Rodrigo da Silva Martins; Angelo Berchieri Junior; Oliveiro Caetano de Freitas Neto (Brazilian Journal of Microbiology, 2022)

Performance and ruminal and intestinal morphometry of Santa Inês sheep submitted to feed restriction and refeeding - Hugo Batista Lima; Roberto Germano Costa; Tairon Pannunzio Dias-Silva; George Rodrigo Beltrão da Cruz; Francisco Fernandes Ramos de Carvalho; Ricardo Romão Guerra; Neila Lidiany Ribeiro; José Teodorico de Araújo Filho; Alfredo J. Costa Teixeira (Tropical Animal Health and Production, 2022)

Modelling the abundance of a non-native mollusk in tropical semi-arid reservoirs - Daniele Jovem-Azevêdo; José Fernandes Bezerra-Neto; Maria João Feio; Rodrigo Fernandes; Wilma Izabelly Ananias Gomes; Sidinei Magela Thomaz; Joseline Molozzi (Hydrobiologia, 2022)

Chronic exposure to lead acetate promotes changes in the alveolar bone of rats: microstructural and physical–chemical characterization - Lodinikki Lemoy Davis; Walessa Alana Bragança Aragão; Géssica de Oliveira Lopes; Luciana Guimaraes Eiró; Alexandre Rodrigues Freire; Felippe Bevilacqua Prado; Ana Cláudia Rossi; Allan da Silva Cruz; Kelly das Graças Fernandes Dantas; Alan Rodrigo Leal Albuquerque; Simone Patricia Aranha Paz; Rômulo Simões Angélica; et al. (Environmental Science and Pollution Research, 2022)

DNA Metabarcoding from Microbial Communities Recovered from Stream and Its Potential for Bioremediation Processes - Júlia Ronzella Ottoni; Rosane dos Santos Grignet; Maria Gabriela Azevedo Barros; Suzan Prado Fernandes Bernal; Andressa Alves Silva Panatta; Gileno Vieira Lacerda-Júnior; Victor Borin Centurion; Tiago Palladino Delforno; Caroline da Costa Silva Goncalves; Michel Rodrigo Zambrano Passarini (Current Microbiology, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Contrasting continental patterns and drivers of taxonomic and functional turnover among fish assemblages across Brazilian reservoirs - Fernando Mayer Pelicice; Luciana da Silva Damasceno; Eveline de Almeida Ferreira; Weferson Júnio da Graça; Carlos Sérgio Agostinho; Rodrigo Fernandes (Hydrobiologia, 2022)

Impact of copper sulfate on survival, behavior, midgut morphology, and antioxidant activity of Partamona helleri (Apidae: Meliponini) - Rodrigo Cupertino Bernardes; Kenner Morais Fernandes; Daniel Silva Sena Bastos; André Filipe Penha Aires Freire; Marcos Pereira Lopes; Leandro Licursi de Oliveira; Mara Garcia Tavares; Renan dos Santos Araújo; Gustavo Ferreira Martins (Environmental Science and Pollution Research, 2022)

Gliotoxicity and Glioprotection: the Dual Role of Glial Cells - André Quincozes-Santos; Camila Leite Santos; Rômulo Rodrigo de Souza Almeida; Amanda da Silva; Natalie K. Thomaz; Naithan Ludian Fernandes Costa; Fernanda Becker Weber; Izaviany Schmitz; Lara Scopel Medeiros; Lívia Medeiros; Bethina Segabinazzi Dotto; Filipe Renato Pereira Dias; et al. (Molecular Neurobiology, 2021)

Behavioral, neuroplasticity and metabolic effects of 7,8-dihydroxy-4-methylcoumarin associated with physical activity in mice - Priscilla Karla Fernandes Lopes; Daiane Fátima Engel; Natalia Oliveira Bertolini; Moisés Silvestre de Azevedo Martins; Chrystian Araujo Pereira; Licio Augusto Velloso; Sérgio Scherrer Thomasi; Rodrigo Ferreira de Moura (Metabolic Brain Disease, 2021)

Photocatalytic degradation of Novacron blue and Novacron yellow textile dyes by the TiO2/palygorskite nanocomposite - Mikaely Lizandra Moreira de Assis; Elmar Damasceno Junior; Janiele Mayara Ferreira de Almeida; Isabel do Nascimento Silva; Rodrigo Victor Barbosa; Lamara Maciel dos Santos; Elizete Faustino Dias; Nedja Suely Fernandes; Carlos Alberto Martinez-Huitle (Environmental Science and Pollution Research, 2021)

Novel alphaherpesvirus in a wild South American sea lion (Otaria byronia) with pulmonary tuberculosis - Carlos Sacristán; Samira Costa-Silva; Laura Reisfeld; Pedro Enrique Navas-Suárez; Ana Carolina Ewbank; Aricia Duarte-Benvenuto; Natália Coelho Couto de Azevedo Fernandes; Rodrigo Albergaria Ressio; Marzia Antonelli; Janaina Rocha Lorenço; Cíntia Maria Favero; Juliana Marigo; et al. (Brazilian Journal of Microbiology, 2021)

Cognitive impairment in the HTLV-1 infection: a comparative study associated with functional performance - Jonas Jardim de Paula; Luiz Claúdio Romanelli; Renata Caetano Vieira de Faria; Anna Barbara Proietti; Leandro Fernandes Malloy-Diniz; Marco Aurélio Romano-Silva; Debora Marques de Miranda; Rodrigo Nicolato (Journal of NeuroVirology, 2021)

Conservation conflicts and their drivers in different protected area management groups: a case study in Brazil - Wanderley Jorge da Silveira-Junior; Cléber Rodrigo de Souza; Ravi Fernandes Mariano; Carolina Corrêa Santos Moura; Carolina Costa Rodrigues; Marco Aurélio Leite Fontes (Biodiversity and Conservation, 2021)

The extracellular matrix protein Agrin is expressed by osteoblasts and contributes to their differentiation - Alann Thaffarell Portilho Souza; Helena Bacha Lopes; Fabiola Singaretti Oliveira; Denise Weffort; Gileade Pereira Freitas; Leticia Faustino Adolpho; Roger Rodrigo Fernandes; Adalberto Luiz Rosa; Marcio Mateus Beloti (Cell and Tissue Research, 2021)

Global phylogeography of sailfish: deep evolutionary lineages with implications for fisheries management - Bruno Lopes da Silva Ferrette; Bruno Mourato; Fábio Hissa Vieira Hazin; Freddy Arocha; Samuel Mackey Williams; Carlos Egberto Rodrigues Junior; Fábio Porto-Foresti; Alberto Ferreira de Amorim; Matheus Marcos Rotundo; Rui Coelho; John P. Hoolihan; Fambaye Ngom Sow; et al. (Hydrobiologia, 2021)

Antimicrobial activity against Microcystis aeruginosa and degradation of microcystin-LR by bacteria isolated from Antarctica - Gabriela Rocío Sosa Benegas; Suzan Prado Fernandes Bernal; Valéria Maia de Oliveira; Michel Rodrigo Zambrano Passarini (Environmental Science and Pollution Research, 2021)

Large-scale Degradation of the Tocantins-Araguaia River Basin - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Alberto Akama; José Dilermando Andrade Filho; Valter M. Azevedo-Santos; Marcus Vinicius Moreira Barbosa; Luis Mauricio Bini; Marcelo Fulgêncio Guedes Brito; Carlos Roberto dos Anjos Candeiro; Érica Pellegrini Caramaschi; Priscilla Carvalho; Rodrigo Assis de Carvalho; et al. (Environmental Management, 2021)

Correction to: Performance, biochemical and physiological parameters of Dorper × Santa Ines lambs fed with three levels of metabolizable energy - Angélica Bonafede Martins Teixeira; Bruno Raphael Fasolli Schuh; Veridiana Lourenço Daley; Pedro Henrique Nicolau Pinto; Sergio Rodrigo Fernandes; José Antônio de Freitas (Tropical Animal Health and Production, 2021)

Pharmaceutical biotechnological potential of filamentous fungi isolated from textile industry - Suzan Prado Fernandes Bernal; Micaela Andrea Gritti; Viviane Piccin dos Santos; Júlia Ronzella Ottoni; Valéria Maia de Oliveira; Maria Elisa Peichoto; Michel Rodrigo Zambrano Passarini (Archives of Microbiology, 2021)

Reconstruction of Marine Commercial Landings for the Brazilian Industrial and Artisanal Fisheries From 1950 to 2015 - Kátia Meirelles Felizola Freire; Zafira da Silva de Almeida; José Raimundo Emanoel Trindade Amador; José Augusto Aragão; Ana Rosa da Rocha Araújo; Antônio Olinto Ávila-da-Silva; Bianca Bentes; Marcus Henrique Carneiro; Julien Chiquieri; Cezar Augusto Freire Fernandes; Marina Bezerra Figueiredo; Maurício Hostim-Silva; et al. (Frontiers in Marine Science, 2021)
Landing data are the most basic information used to manage fisheries, although they are often unavailable or incomplete. The objective of this work was to reconstruct the national database of marine commercial landings for the Brazilian industrial and artisanal fisheries, from 1950 to 2015. Total landings increased strongly from 1950 to mid-1980s and suffered sharp decline in the early 1990s, mainly associated to the collapse of sardine fisheries. After that, another period of increasing landings was observed, but at a much lower rate. Industrial landings always surpassed artisanal landings in Brazilian waters, except for the beginning of the time series, when many industrial fleets had not started yet, and in the early 2000s, when a change in the methodology for collecting landing statistics was implemented in the state of Pará leading to an overestimation of artisanal landings. Artisanal fisheries have been declining since 2005, which is worrisome due to the social impact it may have on local income and food security. Regional differences were also observed, with industrial landings being always higher than artisanal landings in southeastern-southern Brazil, while the opposite was true for the northern-northeastern regions. Higher landings were observed in the southeastern-southern regions when both artisanal and industrial fleets were combined. Sardine and demersal fishes were the main resources landed by industrial fishers. Artisanal fishers caught more species than their industrial counterpart, featuring Xiphopenaeus kroyeri , Cynoscion acoupa , and Ucides cordatus . Although the fishing of Epinephelus itajara was banned in Brazil, it continues to be landed. Yet, catches of this species and others under some threat status are still not properly registered, including: Carcharhinus longimanus , Galeorhinus galeus , Sphyrna lewini , Sphyrna mokarran , Pristis pectinata , and Pseudobatos horkelii . Fishing resources not identified in previous landing reconstruction efforts, such as sea urchins and sea cucumbers, have now been reported. The database presented here should be continuously updated and improved. It is of paramount importance to resume the collection of landing statistics, including information on fishing effort, to assess the relative impact of fisheries and environmental factors on the main Brazilian fishing stocks.

Performance, biochemical and physiological parameters of Dorper × Santa Ines lambs fed with three levels of metabolizable energy - Angélica Bonafede Martins Teixeira; Bruno Raphael Fasolli Schuh; Veridiana Lourenço Daley; Pedro Henrique Nicolau Pinto; Sergio Rodrigo Fernandes; José Antônio de Freitas (Tropical Animal Health and Production, 2021)

Ancestry analysis indicates two different sets of essential genes in eukaryotic model species - Iara D. de Souza; Clovis F. Reis; Diego A. A. Morais; Vítor G. S. Fernandes; João Vitor F. Cavalcante; Rodrigo J. S. Dalmolin (Functional & Integrative Genomics, 2021)

Physicochemical, microbiological quality, and risk assessment of water consumed by a quilombola community in midwestern Brazil - Paulo Sérgio Scalize; Ellen Flávia Moreira Gabriel; Fernando Santos Lima; Poliana Nascimento Arruda; Hítalo Tobias Lôbo Lopes; Ysabella Paula Reis; Lilian Carla Carneiro; Nolan Ribeiro Bezerra; Fabíola Souza Fiaccadori; Luis Rodrigo Fernandes Baumann (Environmental Science and Pollution Research, 2021)

Potential of Bacterial Strains Isolated from Ironstone Outcrops Bromeliads to Promote Plant Growth Under Drought Conditions - Rodrigo Mattos Silva Galeano; Fernanda Maria de Russo Godoy; Laís Mayara Melo Duré; Paulo Ivan Fernandes-Júnior; José Ivo Baldani; Gecele Matos Paggi; Fabiana Fonseca Zanoelo; Marivaine Silva Brasil (Current Microbiology, 2021)

A New Species of Liosphex Townes, 1977 (Hymenoptera: Rhopalosomatidae) from the Amazon Forest and New Records for the Genus in Brazil - Mayara Medeiros Bulbol; Alexandre Somavilla; Daniell Rodrigo Rodrigues Fernandes; Pedro Reck Bartholomay (Neotropical Entomology, 2021)

From molecule to conservation: DNA-based methods to overcome frontiers in the shark and ray fin trade - Rodrigo Rodrigues Domingues; Ingrid Vasconcellos Bunholi; Danillo Pinhal; Agostinho Antunes; Fernando Fernandes Mendonça (Conservation Genetics Resources, 2021)

Comparative functional responses predict the predatory impact of the highly invasive fish Cichla kelberi - Thiago Lima Carvalho; Eveline de Almeida Ferreira; Fernando Mayer Pelicice; Rodrigo Fernandes (Hydrobiologia, 2021)

Fifty years of Neotropical Entomology - Eliana Maria Gouveia Fontes; Raul Alberto Laumann; Daniell Rodrigo Rodrigues Fernandes; Antônio Ricardo Panizzi (Neotropical Entomology, 2021)

Preadministration of yerba mate (Ilex paraguariensis) helps functional activity and morphology maintenance of MC3T3-E1 osteoblastic cells after in vitro exposition to hydrogen peroxide - Gabrielli Collasanto Ceverino; Paula Katherine Vargas Sanchez; Roger Rodrigo Fernandes; Guilherme Alvarenga Alves; José Bernardo de Santis; Milla Sprone Tavares; Selma Siéssere; Karina Fittipaldi Bombonato-Prado (Molecular Biology Reports, 2021)

Long-term responses of fish diversity to river regulation: a multi-metric approach - Hasley Rodrigo Pereira; Leonardo Fernandes Gomes; Philip Teles Soares; Pedro Ribeiro Martins; Fernando Mayer Pelicice; Fabrício Barreto Teresa; Ludgero Cardoso Galli Vieira (Environmental Biology of Fishes, 2021)

Rosmarinic acid prevents gastric ulcers via sulfhydryl groups reinforcement, antioxidant and immunomodulatory effects - Raphaela Francelino do Nascimento; Rodrigo de Oliveira Formiga; Flávia Danielle Frota Machado; Igor Rafael Praxedes de Sales; Gedson Moraes de Lima; Edvaldo Balbino Alves Júnior; Giciane Carvalho Vieira; Raquel Fragoso Pereira; Aurigena Antunes de Araújo; Raimundo Fernandes de Araújo Junior; José Maria Barbosa Filho; Leônia Maria Batista (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Evaluation of the Fermentative Capacity of Saccharomyces cerevisiae CAT-1 and BB9 Strains and Pichia kudriavzevii BB2 at Simulated Industrial Conditions - Adriana Menezes Olivo Fernandes; Nayara Fernanda Lisbôa Garcia; Gustavo Graciano Fonseca; Rodrigo Simões Ribeiro Leite; Marcelo Fossa da Paz (Indian Journal of Microbiology, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Forest cover influences zooplanktonic communities in Amazonian streams - Ana Caroline Alcântara Missias Gomes; Leonardo Fernandes Gomes; Iris Roitman; Hasley Rodrigo Pereira; Antonio Felipe Couto Junior; Elizabeth Maria Mamede da Costa; Mariana Lessa Carneiro da Silva; Tamiel Khan Baiocchi Jacobson; Rômulo José da Costa Ribeiro; Reinaldo José de Miranda Filho; Mario Lucio de Avila; Ludgero Cardoso Galli Vieira (Aquatic Ecology, 2020)

Undecane production by cold-adapted bacteria from Antarctica - Michel Rodrigo Zambrano Passarini; Tiago Rodrigues e Silva; Suzan Prado Fernandes Bernal; Nathália Luana Cecchet; Adilson Sartoratto; Marcela Boroski; Alysson Wagner Fernandes Duarte; Júlia Ronzella Ottoni; Luiz Henrique Rosa; Valéria Maia de Oliveira (Extremophiles, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Correction to: A role for mast cells and mast cell tryptase in driving neutrophil recruitment in LPS-induced lung inflammation via protease-activated receptor 2 in mice - Aline Dias de Almeida; Irismara Sousa Silva; Weslley Fernandes-Braga; Antônio Carlos Melo LimaFilho; Rodrigo Machado Florentino; Ayslan Barra; Luciana de Oliveira Andrade; M. Fátima Leite; Geovanni Dantas Cassali; André Klein (Inflammation Research, 2020)

5 km front crawl in pool and open water swimming: breath-by-breath energy expenditure and kinematic analysis - Rodrigo Zacca; Vânia Neves; Tiago da Silva Oliveira; Susana Soares; Luís Manuel Pinto Lopes Rama; Flávio Antônio de Souza Castro; João Paulo Vilas-Boas; David B. Pyne; Ricardo J. Fernandes (European Journal of Applied Physiology, 2020)

Phylogenetic beta diversity in an upper montane Atlantic Forest along an altitudinal gradient - Ravi Fernandes Mariano; Vanessa Leite Rezende; Carolina Njaime Mendes; Rubens Manoel dos Santos; Cléber Rodrigo de Souza; Aloysio Souza de Moura; Felipe Santana Machado; Patrícia Vieira Pompeu; Warley Augusto Caldas Carvalho; Marco Aurélio Leite Fontes (Plant Ecology, 2020)

Correlations and repeatability between Babesia spp. infection levels using two dairy cattle breeding systems - Rodrigo Giglioti; Henrique Nunes de Oliveira; Gunta Gutmanis; Guilherme Favero Luciani; Bianca Tainá Azevedo; Cristiane Fernandes de Carvalho Fiorin; Mariana Fogale de Andrade; Marco Antônio Faria Silva; Anibal Eugênio Vercesi Filho; Luciana Morita Katiki; Cintia Hiromi Okino; Márcia Cristina de Sena Oliveira; et al. (Experimental and Applied Acarology, 2020)

Toxicity of Biocide Formulations in the Soil to the Gut Community in Balloniscus selowii Brandt, 1983 (Crustacea: Isopoda: Oniscidea) - Lisiane Martins Volcão; Letícia Schmidt Fraga; Rodrigo de Lima Brum; Renata Rodrigues de Moura; Eduardo Bernardi; Daniela Fernandes Ramos; Flávio Manoel Rodrigues da Silva Júnior (Water, Air, & Soil Pollution, 2020)

Short communication: Bacillus subtilis C-3102 improves biomass gain, innate defense, and intestinal absorption surface of native Brazilian hybrid Surubim (Pseudoplatystoma corruscans x P. reticulatum) - Pamela Thainara do Nascimento Veiga; Marco Shizuo Owatari; André Luiz Nunes; Robson Andrade Rodrigues; Rodrigo Y. Dichoff Kasai; Carlos Eurico Fernandes; Cristiane Meldau de Campos (Aquaculture International, 2020)

Research on dams and fishes: determinants, directions, and gaps in the world scientific production - Hasley Rodrigo Pereira; Leonardo Fernandes Gomes; Hugo de Oliveira Barbosa; Fernando Mayer Pelicice; João Carlos Nabout; Fabrício Barreto Teresa; Ludgero Cardoso Galli Vieira (Hydrobiologia, 2020)

Community reassembly after river regulation: rapid loss of fish diversity and the emergence of a new state - Phamela Bernardes Perônico; Carlos Sérgio Agostinho; Rodrigo Fernandes; Fernando Mayer Pelicice (Hydrobiologia, 2020)

Creatine nanoliposome reverts the HPA-induced damage in complex II–III activity of the rats’ cerebral cortex - Nathana Jamille Mezzomo; Diego Becker Borin; Francine Ianiski; Barbara Dotto Fontana; Itiane Diehl de Franceschi; Juliane Bolzan; Renata Garcez; Mateus Grings; Belisa Parmeggiani; Liana da Silva Fernandes; Rodrigo de Almeida Vaucher; Guilhian Leipnitz; et al. (Molecular Biology Reports, 2019)

Arbuscular Mycorrhizal Fungi Associated with Bamboo Under Cerrado Brazilian Vegetation - Jadson Belem de Moura; Rodrigo Fernandes de Souza; Wagner Gonçalves Vieira Junior; Isabelly Ribeiro Lima; Gustavo Henrique Mendes Brito; César Marín (Journal of Soil Science and Plant Nutrition, 2019)

Nanoformulation as a tool for improvement of thiamethoxam encapsulation and evaluation of ecotoxicological impacts - Marcia Regina Assalin; Lucas Daniel Lavansdoski dos Santos; Debora Renata Cassoli de Souza; Maria Aparecida Rosa; Rafaela Rangni Moltocaro Duarte; Rodrigo Fernandes Castanha; Patricia Pulcini Rosvald Donaire; Nelson Durán (Energy, Ecology and Environment, 2019)

DNA-based species identification of shark finning seizures in Southwest Atlantic: implications for wildlife trade surveillance and law enforcement - Bruno Lopes da Silva Ferrette; Rodrigo Rodrigues Domingues; Luis Henrique Fregadolli Ussami; Letícia Moraes; Carolina de Oliveira Magalhães; Alberto Ferreira de Amorim; Alexandre Wagner Silva Hilsdorf; Claudio Oliveira; Fausto Foresti; Fernando Fernandes Mendonça (Biodiversity and Conservation, 2019)

Quantification of ovine herpesvirus 2 by digital PCR in an outbreak of malignant catarrhal fever - Tatiana Flávia Pinheiro de Oliveira; Mateus Laguardia-Nascimento; Fabiana Galtarossa Xavier; Carla do Amaral Pinto; Luciana Rabello Ferreira; Ivy de Castro Campos de Souza; Márcia Elisa Hammerschmitt; Ronaldo Michel Bianchi; Júlia Gabriela Wronski; Rodrigo Nestor Etges; Grazziane Maciel Rigon; Marcelo Fernandes Camargos; et al. (Archives of Virology, 2019)

Oral delivery of pancreatitis‐associated protein by Lactococcus lactis displays protective effects in dinitro‐benzenesulfonic‐acid‐induced colitis model and is able to modulate the composition of the microbiota - Natalia M. Breyner; Priscilla Bagano Vilas Boas; Gabriel Fernandes; Rodrigo D. de Carvalho; Tatiana Rochat; Marie‐Laure Michel; Florian Chain; Harry Sokol; Marcela de Azevedo; Anderson Myioshi; Vasco A. Azevedo; Philippe Langella; et al. (Environmental Microbiology, 2019)
Summary Antimicrobial peptides secreted by intestinal immune and epithelial cells are important effectors of innate immunity. They play an essential role in the maintenance of intestinal homeostasis by limiting microbial epithelium interactions and preventing unnecessary microbe‐driven inflammation. Pancreatitis‐associated protein (PAP) belongs to Regenerating islet‐derived III proteins family and is a C‐type (Ca +2 dependent) lectin. PAP protein plays a protective effect presenting anti‐inflammatory properties able to reduce the severity of colitis, preserving gut barrier and epithelial inflammation. Here, we sought to determine whether PAP delivered at intestinal lumen by recombinant Lactococcus lactis strain (LL‐PAP) before and after chemically induced colitis is able to reduce the severity in two models of colitis. After construction and characterization of our recombinant strains, we tested their effects in dinitro‐benzenesulfonic‐acid (DNBS) and Dextran sulfate sodium (DSS) colitis model. After the DNBS challenge, mice treated with LL‐PAP presented less severe colitis compared with PBS and LL‐empty‐treated mice groups. After the DSS challenge, no protective effects of LL‐PAP could be detected. We determined that after 5 days administration, LL‐PAP increase butyrate producer's bacteria, especially Eubacterium plexicaudatum . Based on our findings, we hypothesize that a treatment with LL‐PAP shifts the microbiota preventing the severity of colon inflammation in DNBS colitis model. These protective roles of LL‐PAP in DNBS colitis model might be through intestinal microbiota modulation.

Genetic characterization of a putative new type of bovine papillomavirus in the Xipapillomavirus 1 species in a Brazilian dairy herd - Sarah Elizabeth Izzo Crespo; Michele Lunardi; Rodrigo Alejandro Arellano Otonel; Selwyn Arlington Headley; Alice Fernandes Alfieri; Amauri Alcindo Alfieri (Virus Genes, 2019)

ATLANTIC MAMMALS : a data set of assemblages of medium‐ and large‐sized mammals of the Atlantic Forest of South America - Yuri Souza; Fernando Gonçalves; Laís Lautenschlager; Paula Akkawi; Calebe Mendes; Mariana M. Carvalho; Ricardo S. Bovendorp; Hugo Fernandes‐Ferreira; Clarissa Rosa; Maurício Eduardo Graipel; Nivaldo Peroni; Jorge José Cherem; et al. (Ecology, 2019)
Biodiversity inventories contain important information about species richness, community structure, and composition, and are the first step in developing any conservation and mitigation strategies. The Atlantic Forest of South America is home to around 334 species of small‐, medium‐, and large‐sized mammals, and is currently restricted to less than 12% of its original cover. Here, we present the ATLANTIC MAMMALS , an open data set on information on medium‐ and large‐sized mammal assemblages in the Atlantic Forest of Brazil, Paraguay, and Argentina. A total of 129 studies were compiled, including published and in press peer‐reviewed papers, book chapters, theses and unpublished data. We mapped 244 assemblages, eight orders, 63 genera, and 94 species (24 of which are classified as threatened by the IUCN Red List) distributed in 128 protected and 116 unprotected areas. Species richness of the mammalian assemblages varied from 1 to 39 species (mean 15). The most recorded species in the entire biome was Dasypus novemcinctus , followed by Cerdocyon thous and Procyon cancrivorous . These data can be useful in support of macroecological studies and conservation planning strategies. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Increased DNA damage is not associated to polymorphisms in OGGI DNA repair gene, CYP2E1 detoxification gene, and biochemical and hematological findings in soybeans farmers from Central Brazil - Fernanda Ribeiro Godoy; Hugo Freire Nunes; Alessandro Arruda Alves; Wanessa Fernandes Carvalho; Fernanda Craveiro Franco; Rodrigo Roncato Pereira; Alex Silva da Cruz; Cláudio Carlos da Silva; Rogério Pereira Bastos; Daniela de Melo e Silva (Environmental Science and Pollution Research, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Zooplankton functional-approach studies in continental aquatic environments: a systematic review - Leonardo Fernandes Gomes; Hasley Rodrigo Pereira; Ana Caroline Alcântara Missias Gomes; Maisa Carvalho Vieira; Pedro Ribeiro Martins; Iris Roitman; Ludgero Cardoso Galli Vieira (Aquatic Ecology, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Ecotoxicological evaluation of electrochemical oxidation for the treatment of sanitary landfill leachates - Annabel Fernandes; Manuel Ramiro Pastorinho; Ana Catarina Sousa; Wilson Silva; Rodrigo Silva; Maria João Nunes; Ana Sofia Rodrigues; Maria José Pacheco; Lurdes Ciríaco; Ana Lopes (Environmental Science and Pollution Research, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Unusual Intestinal Involvement by Paracoccidioidomycosis Diagnosed After Oral Manifestation - Rodrigo Neves-Silva; Patrícia Maria Fernandes; Alan Roger Santos-Silva; Pablo Agustin Vargas; Ricardo de Souza Cavalcante; Marcio Ajudarte Lopes (Mycopathologia, 2018)

Linking Biodiversity, the Environment and Ecosystem Functioning: Ecological Functions of Dung Beetles Along a Tropical Elevational Gradient - Cássio Alencar Nunes; Rodrigo Fagundes Braga; Fernando de Moura Resende; Frederico de Siqueira Neves; José Eugênio Cortes Figueira; G. Wilson Fernandes (Ecosystems, 2018)

Heme oxygenase-1/biliverdin/carbon monoxide pathway downregulates hypernociception in rats by a mechanism dependent on cGMP/ATP-sensitive K+ channels - Hellíada Vasconcelos Chaves; Danielle Rocha do Val; Kátia Alves Ribeiro; Jonas Cavalcante Lemos; Ricardo Basto Souza; Francisco Isaac Fernandes Gomes; Rodrigo Maranguape Silva da Cunha; Vicente de Paulo Teixeira Pinto; Gerardo Cristino Filho; Marcellus Henrique Loiola Ponte de Souza; Mirna Marques Bezerra; Gerly Anne de Castro Brito (Inflammation Research, 2018)

Deltamethrin-induced nuclear erythrocyte alteration and damage to the gills and liver of Colossoma macropomum - Fernanda dos Santos Cunha; Natalino da Costa Sousa; Rudã Fernandes Brandão Santos; Juliana Oliveira Meneses; Márcia Valéria Silva do Couto; Fabrício Tavares Cunha de Almeida; José Guedes de Sena Filho; Paulo César Falanghe Carneiro; Alexandre Nizio Maria; Rodrigo Yudi Fujimoto (Environmental Science and Pollution Research, 2018)

The semi-synthetic molecule [4″,5″] dihydro-obovatin isolated from Tephrosia Toxicaria pers reduces zymosan-induced temporomandibular joint inflammatory hypernociception in rats - Danielle Rocha do Val; Hellíada Vasconcelos Chaves; Francisco Isaac Fernandes Gomes; Rodrigo da Silva Santos; Antonio Mateus Gomes Pereira; Igor Iuco Castro da Silva; Vicente de Paulo Teixeira Pinto; Lissiana Magna Vasconcelos Aguiar; Norma Maria Barros Benevides; Francisca Renata Lopes da Silva; Jair Mafezoli; Jackson Nunes e Vasconcelos; et al. (Medicinal Chemistry Research, 2018)

Anti-inflammatory and antialgic actions of a nanoemulsion of Rosmarinus officinalis L. essential oil and a molecular docking study of its major chemical constituents - Raphaelle Sousa Borges; Emerson Silva Lima; Hady Keita; Irlon Maciel Ferreira; Caio Pinho Fernandes; Rodrigo Alves Soares Cruz; Jonatas Lobato Duarte; Josué Velázquez-Moyado; Brenda Lorena Sánchez Ortiz; Andrés Navarrete Castro; Jaderson Vieira Ferreira; Lorane Izabel da Silva Hage-Melim; et al. (Inflammopharmacology, 2018)

The great biotechnological potential of a marine polychaete: An alliance between toxin and natural fluorescence - Ana Rodrigo; Ana Lopes; Pedro Baptista; Maria Costa; Alexandra Fernandes; Pedro Costa (Frontiers in Marine Science, 2018)

Fibroblast contributes for osteoblastic phenotype in a MAPK-ERK and sonic hedgehog signaling-independent manner - Celio J. da Costa Fernandes; Augusto Santana do Nascimento; Rodrigo A. da Silva; Willian F. Zambuzzi (Molecular and Cellular Biochemistry, 2017)

Effluents from Anaerobic Digestion of Organic Wastes: Treatment by Chemical and Electrochemical Processes - Annabel Fernandes; Tatiana Jesus; Rodrigo Silva; Maria José Pacheco; Lurdes Ciríaco; Ana Lopes (Water, Air, & Soil Pollution, 2017)

Chemical sex recognition in the harvestman Discocyrtus prospicuus (Arachnida: Opiliones) - Nathália S. Fernandes; Estefanía Stanley; Fernando G. Costa; Carlos A. Toscano-Gadea; Rodrigo H. Willemart (acta ethologica, 2017)

Deltamethrin as inductor agent of precocious ovarian degeneration in Rhipicephalus sanguineus s.l. (Acari: Ixodidae) ticks - Maria Izabel Camargo-Mathias; Natalia Rubio Claret Pereira; Camila da Silva Reis; Cristiane Regina de Almeida; Douglas Rodrigo dos Santos Mendes; Giselle Bezerra de Araújo; Lays Postali; Tober Figueroa; Allan Roberto Fernandes Ferreira; Juan Parente Santos; Patrícia Rosa de Oliveira (Experimental and Applied Acarology, 2017)

Coupling watersheds, estuaries and regional ocean through numerical modelling for Western Iberia: a novel methodology - Francisco Campuzano; David Brito; Manuela Juliano; Rodrigo Fernandes; Hilda de Pablo; Ramiro Neves (Ocean Dynamics, 2016)

Monitoring Methodology of Interventions for Riverbanks Stabilization: Assessment of Technical Solutions Performance - António Pinto; L. F. Sanches Fernandes; Rodrigo Maia (Water Resources Management, 2016)

Cytokines profile and its correlation with endothelial damage and oxidative stress in patients with type 1 diabetes mellitus and nephropathy - Rodrigo M. C. Pestana; Caroline P. Domingueti; Rita C. F. Duarte; Rodrigo B. Fóscolo; Janice S. Reis; Ana Maria S. Rodrigues; Laís B. Martins; Lirlândia P. Sousa; Daniela P. Lage; Cláudia N. Ferreira; Adaliene V. M. Ferreira; Ana P. Fernandes; et al. (Immunologic Research, 2016)

“Cytochrome c oxidase I DNA sequence of Camponotus ants with different nesting strategies is a tool for distinguishing between morphologically similar species” - Manuela O. F. Ramalho; Rodrigo M. Santos; Tae T. Fernandes; Maria Santina C. Morini; Odair C. Bueno (Genetica, 2016)

Biological and molecular characterization of a highly divergent johnsongrass mosaic virus isolate from Pennisetum purpureum - Karina N. Silva; Fernando L. Melo; Anelise F. Orílio; Tatsuya Nagata; Marilia S. Silva; Celso D. Fernandes; Rodrigo R. Fragoso; Suelen N. Dessaune; Renato O. Resende (Archives of Virology, 2016)

Genetic diversity of bovine papillomavirus types, including two putative new types, in teat warts from dairy cattle herds - Michele Lunardi; Claudia de Camargo Tozato; Alice Fernandes Alfieri; Brígida Kussumoto de Alcântara; Laurival Antonio Vilas-Boas; Rodrigo Alejandro Arellano Otonel; Selwyn Arlington Headley; Amauri Alcindo Alfieri (Archives of Virology, 2016)

Genetic background of novel sequence types of CTX-M-8- and CTX-M-15-producing Escherichia coli and Klebsiella pneumoniae from public wastewater treatment plants in São Paulo, Brazil - Milena Dropa; Nilton Lincopan; Livia C. Balsalobre; Danielle E. Oliveira; Rodrigo A. Moura; Miriam Rodriguez Fernandes; Quézia Moura da Silva; Glavur R. Matté; Maria I. Z. Sato; Maria H. Matté (Environmental Science and Pollution Research, 2016)

Cellular Changes Induced by Kinin B1 Receptor Deletion: Study of Endothelial Nitric Oxide Metabolism - Rodrigo A. Loiola; Tathiany C. Torres; Richardt G. Landgraf; João Bosco Pesquero; Liliam Fernandes (International Journal of Peptide Research and Therapeutics, 2015)

Insights into the mechanisms underlying the antiproliferative potential of a Co(II) coordination compound bearing 1,10-phenanthroline-5,6-dione: DNA and protein interaction studies - Daniel V. Luís; Joana Silva; Ana Isabel Tomaz; Rodrigo F. M. de Almeida; Miguel Larguinho; Pedro V. Baptista; Luísa M. D. R. S. Martins; Telma F. S. Silva; Pedro M. Borralho; Cecília M. P. Rodrigues; António S. Rodrigues; Armando J. L. Pombeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2014)

Geoacoustic character, sedimentology and chronology of a cross-shelf Holocene sediment deposit off Cabo Frio, Brazil (southwest Atlantic Ocean) - Ursula Mendoza; Arthur Ayres Neto; Rodrigo C. Abuchacra; Cátia Fernandes Barbosa; Alberto G. Figueiredo; Manoela C. Gomes; Andre L. Belem; Ramsés Capilla; Ana Luiza S. Albuquerque (Geo-Marine Letters, 2014)

The effect of sex and genotype on growth performance, feed efficiency, and carcass traits of local sheep group Pantaneiro and Texel or Santa Inês crossbred finished on feedlot - Fernando Miranda de Vargas Junior; Charles Ferreira Martins; Guilherme dos Santos Pinto; Marcos Barbosa Ferreira; Hélio de Almeida Ricardo; André Gustavo Leão; Alexandre Rodrigo Mendes Fernandes; Alfredo Teixeira (Tropical Animal Health and Production, 2014)

Neurophysiological Studies and Non-Motor Symptoms Prior to Ataxia in a Patient with Machado–Joseph Disease: Trying to Understand the Natural History of Brain Degeneration - José Luiz Pedroso; Edson Bor-Seng-Shu; Pedro Braga-Neto; Rodrigo Souza Ribeiro; Márcio Luiz Escorcio Bezerra; Lucila B. F. do Prado; Ilza Rosa Batista; Helena Alessi; Manoel Jacobsen Teixeira; Gilberto Mastrocola Manzano; Gilmar Fernandes do Prado; Orlando Graziani Povoas Barsottini (The Cerebellum, 2014)

Use of probiotics intercropped with plant protein diets and their influence on the growth performance and immunological status of Senegalese sole (Solea senegalensis) - Batista Sónia; Faria Paulo; Costas Benjamín; Fernandes Jorge M.; Valente Luísa M.; Ozório Rodrigo O. (Frontiers in Marine Science, 2014)

The pollen of Caesalpinia pyramidalis Tul. is toxic to honeybees (Apis mellifera) - Igor Ricardo Batista Vieira de Melo; Mateus Cardoso da Costa Lages; Diego Passos dos Santos; Patrício Borges Maracajá; Rodrigo Alboim de Paiva Fernandes Rodrigues; Benito Soto-Blanco (Arthropod-Plant Interactions, 2013)

Spatial and temporal variation of the ichthyoplankton in a subtropical river in Brazil - David Augusto Reynalte-Tataje; Angelo Antônio Agostinho; Andrea Bialetzki; Samara Hermes-Silva; Rodrigo Fernandes; Evoy Zaniboni-Filho (Environmental Biology of Fishes, 2012)

In vitro predatory activity of nematophagous fungi Duddingtonia flagrans on infective larvae of Oesophagostomum spp. after passing through gastrointestinal tract of pigs - Sebastião Rodrigo Ferreira; Jackson Victor de Araújo; Fabio Ribeiro Braga; Juliana Milani Araujo; Fernanda Mara Fernandes (Tropical Animal Health and Production, 2011)

Treatment of experimental periodontal disease by a selective inhibitor of cyclooxygenase-2 with scaling and root planing (SRP) - Valdir Gouveia Garcia; Rodrigo Yuji Takano; Leandro Araújo Fernandes; Juliano Milanezi de Almeida; Leticia Helena Theodoro (Inflammopharmacology, 2010)

The autonomous Simpatico system for real-time continuous water-quality and current velocity monitoring: examples of application in three Portuguese estuaries - Erwan Garel; Susana Nunes; João Magalhães Neto; Rodrigo Fernandes; Ramiro Neves; João Carlos Marques; Óscar Ferreira (Geo-Marine Letters, 2009)

Temporal organization of fish assemblages in floodplain lagoons: the role of hydrological connectivity - Rodrigo Fernandes; Luiz Carlos Gomes; Fernando Mayer Pelicice; Angelo Antonio Agostinho (Environmental Biology of Fishes, 2009)

Fire‐related traits for plant species of the Mediterranean Basin - S. Paula; M. Arianoutsou; D. Kazanis; Ç Tavsanoglu; F. Lloret; C. Buhk; F. Ojeda; B. Luna; J. M. Moreno; A. Rodrigo; J. M. Espelta; S. Palacio; et al. (Ecology, 2009)
Plant trait information is essential for understanding plant evolution, vegetation dynamics, and vegetation responses to disturbance and management. Furthermore, in Mediterranean ecosystems, changes in fire regime may be more relevant than direct changes in climatic conditions, making the knowledge of fire‐related traits especially important. Thus the purpose of this data set was to compile the most updated and comprehensive information on fire‐related traits for vascular plant species of the Mediterranean Basin, that is, traits related to plant persistence and regeneration after fire. Data were collected from an extensive literature review and from field and experimental observations. The data source is documented for each value. Since life history traits may vary spatially or with environmental conditions, we did not aggregate them by species; i.e., traits and species are repeated in different records if they were observed by different researchers and/or in different locations. Life history traits included in the data set are: life form, resprouting ability (after fire, after clipping, or after other disturbances that remove all the aboveground biomass), resprouting bud source, heat‐stimulated germination, other germination cues, seed bank location and longevity, post‐fire seedling emergence and survival, maturity age of resprouts and saplings, and seed mass. Several traits are unknown for many species; consequently, the data set reflects the state of the knowledge on the topic. However, since the ability to resprout is a trait of paramount relevance in fire‐prone environments, it was considered a core trait in the data set, and thus species whose resprouting capacity was unknown were not included. Life form is also provided for all taxa. The structure of the database allows different levels of information (and accuracy) for each entry, and thus some traits may include different types of data (quantitative, semi‐quantitative, or categorical) from different sources. The data set is structured in 8263 records and 11 columns, obtained from 301 published and unpublished sources of information. It includes 952 taxa determined at specific or infraspecific level, which comprise 859 species, 384 genera, and 79 families. Although this is the most comprehensive data set of fire‐relevant plant traits for Mediterranean species, there is still a considerable need for observations and experiments, especially in little‐studied Mediterranean areas, such as northern Africa. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

PAF-induced kinin B1 receptor in vivo up-regulation: involvement of distinct kinase pathways - Elizabeth S. Fernandes; Rodrigo Medeiros; Maria M. Campos; Joao B. Calixto (Inflammation Research, 2007)